Thermosetting resin composition for thermal conductive material, cured product thereof, electronic parts and electronic equipment

A thermosetting resin composition with specific binder components and fillers addresses the challenge of low thermal conductivity and dielectric properties in electronic devices, enhancing heat dissipation and signal transmission in high-frequency environments.

JP7615548B2Active Publication Date: 2025-01-17TOYO INK MFG CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020096295
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-04
Filing Date
2020-06-02
Publication Date
2025-01-17
Estimated Expiration
2040-06-02

AI Technical Summary

Technical Problem

Existing resin compositions used in electronic devices have low thermal conductivity and poor dielectric properties, especially at high frequencies, making it difficult to efficiently dissipate heat and transmit electrical signals in advanced electronic components.

Method used

A thermosetting resin composition containing specific binder components such as styrenic elastomers, polyamide resins, and polyimide resins, combined with thermally conductive fillers, which provide excellent thermal conductivity and dielectric properties, including a dielectric constant of 4.0 or less and a dielectric loss tangent of 0.010 or less at 5 GHz and 23°C.

Benefits of technology

The composition effectively dissipates heat and maintains signal transmission integrity in high-frequency applications, offering improved reliability and performance in electronic components and devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615548000001
    Figure 0007615548000001
  • Figure 0007615548000002
    Figure 0007615548000002
  • Figure 0007615548000003
    Figure 0007615548000003
Patent Text Reader

Abstract

To provide a thermally conductive thermosetting resin composition and a cured product of the composition having excellent thermal conductivity and dielectric characteristics and high reliability, an electronic component and an electronic apparatus.SOLUTION: A thermosetting resin composition for a thermally conductive material is provided, which comprises a binder component and a thermally conductive filler. The binder component is a binder component (I) containing a styrene-based elastomer (P1) having a carboxylic acid anhydride group and a polyisocyanate component (C1), a binder component (II) containing a polyamide resin (P2) having a phenolic hydroxyl group in a side group and a compound (C2) having three or more functional groups, a binder component (III) containing a specific polyurethane resin (P3) and an epoxy compound (C3), or a binder component (IV) containing a specific polyimide resin (P4) and a compound (C4) having two or more functional groups. The cured product shows a relative permittivity of 4.0 or less and a dielectric loss tangent of 0.010 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermosetting resin composition for thermal conductive materials and a cured product thereof, and also to an electronic component having a cured product of the thermosetting resin composition for thermal conductive materials, and an electronic device having the electronic component. [Background technology]

[0002] As integrated circuits become denser, the amount of heat generated inside electronic devices tends to increase, and there is a demand for technology that can diffuse the heat generated inside electronic components more efficiently than ever before. In particular, resin materials are widely used inside electronic devices for the purpose of reducing weight, but the thermal conductivity of resin materials is generally lower than that of metals, ceramics, etc., and therefore there is a demand for resin compositions with excellent thermal conductivity.

[0003] A known example of a resin-based heat dissipation sheet is one in which a heat conductive filler is dispersed in silicone rubber. In addition, a heat-resistant elastic material in which a good heat conductive material is added to a silicone polymer precursor (Patent Document 1) and a resin composition containing a specific boron nitride powder (Patent Document 2) have been proposed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-209955 A [Patent Document 2] JP 2014-40341 ​​A Summary of the Invention [Problem to be solved by the invention]

[0005] While there is a demand for resin compositions with excellent thermal conductivity, the frequency band of signals used in printed wiring boards and the like is shifting from the megahertz range to the gigahertz range, and the higher the frequency, the greater the transmission loss of the electrical signal. Therefore, there is a demand for resin compositions with excellent dielectric properties in high frequency bands.

[0006] The present invention has been made in view of the above background, and an object of the present invention is to provide a highly reliable thermally conductive thermosetting resin composition having excellent thermal conductivity and dielectric properties, and a cured product thereof, an electronic component, and an electronic device. [Means for solving the problem]

[0007] As a result of extensive investigations, the inventors have found that the problems of the present embodiment can be solved in the following aspect, and have completed the present invention. [1]: A thermosetting resin composition for a thermal conductive material, comprising a binder component including a thermosetting resin and a curing agent, and a thermally conductive filler, The binder component is a binder component (I) containing a styrene-based elastomer (P1) having a carboxylic acid anhydride group and a polyisocyanate component (C1) that reacts with the anhydride group; a binder component (II) containing a polyamide resin (P2) having a phenolic hydroxyl group in a side group and a tri- or higher functional compound (C2) capable of reacting with the phenolic hydroxyl group; a binder component (III) containing a polyurethane resin (P3) having a carboxyl group and an epoxy compound (C3) capable of reacting with the carboxyl group, or a binder component (IV) containing a polyimide resin (P4) having a reactive functional group and including a hydrocarbon group having 20 to 60 carbon atoms, and a bifunctional or higher functional compound (C4) that reacts with the reactive functional group; The cured product obtained by curing the thermosetting resin composition for a thermal conductive material is The dielectric constant is 4.0 or less at a frequency of 5 GHz and 23°C. The dielectric tangent is 0.010 or less at a frequency of 5 GHz and 23°C. A thermosetting resin composition for use as a thermal conductive material. [2] Styrenic elastomer (P1) is a block copolymer having at least one of a structural unit derived from an olefin and a structural unit derived from a conjugated diene, and a structural unit derived from styrene; and the polyisocyanate component (C1) is an isocyanate group-containing compound having two or more isocyanates; Polyamide resin (P2) is The polyamide resin (P2) satisfies the following (i) and / or (ii), and further, the polyamide resin (P2) of (i) satisfies the following (iii) and (vi), and the polyamide resin (P2) of (ii) satisfies the following (iv) to (vi), The compound (C2) satisfies the following (vii), The polyurethane resin (P3) is a polyurethane polyurea resin, the polyimide resin (P4) contains structural units derived from an aromatic carboxylic polyanhydride and structural units derived from a polyamine compound having a hydrocarbon group having 20 to 60 carbon atoms, and 70 mass % or more of the hydrocarbon group having 20 to 60 carbon atoms is a group derived from a dimer skeleton, the reactive functional groups are amine and / or anhydride groups; The thermosetting resin composition for a thermal conductive material according to [1], wherein the di- or higher functional compound (C4) is an epoxy compound. (i) The polyamide resin (P2) is a polyamide (A-1) in which the phenolic hydroxyl group and a hydrocarbon group having 20 to 60 carbon atoms (but excluding the aromatic ring to which the phenolic hydroxyl group is bonded) are contained within the same polymer. (ii) The polyamide resin (P2) is a polyamide (A-3) obtained by mixing a polyamide (a-1) containing a phenolic hydroxyl group in a side group and a polyamide (a-2) containing a hydrocarbon group having 20 to 60 carbon atoms. (iii) Monomers constituting the polyamide (A-1) include a monomer having a phenolic hydroxyl group and a monomer having a hydrocarbon group having 20 to 60 carbon atoms. (iv) The polybasic acid monomer and / or polyamine monomer constituting the polyamide (a-1) contains a monomer having a phenolic hydroxyl group, and the polybasic acid monomer and the polyamine monomer do not contain a monomer having a hydrocarbon group having 20 to 60 carbon atoms. (v) The polybasic acid monomer and / or the polyamine monomer constituting the polyamide (a-2) contain a monomer having a hydrocarbon group having 20 to 60 carbon atoms, and the polybasic acid monomer and the polyamine monomer do not contain a monomer having a phenolic hydroxyl group. (vi) At least a part of the monomers having a hydrocarbon group with 20 to 60 carbon atoms includes a compound having a cyclic structure with 5 to 10 carbon atoms. (vii) The compound (C2) is at least one member selected from the group consisting of an epoxy group-containing compound, an isocyanate group-containing compound, a carbodiimide group-containing compound, a metal chelate, a metal alkoxide, and a metal acylate. [3]: The thermosetting resin composition for a thermal conductive material according to [1] or [2], wherein the thermal conductive filler is at least one selected from the group consisting of alumina, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, calcium oxide, magnesium oxide, zinc oxide, beryllia, aluminum oxide, aluminum nitride, boron nitride, fused silica, crystalline silica, amorphous silica, silicon carbide, silicon nitride, titanium carbide, and diamond. [4]: The thermosetting resin composition for a thermal conductive material according to any one of [1] to [3], which is in the form of a powder, a film, a sheet, a plate, a pellet, a paste, or a liquid. [5]: A cured product of the thermosetting resin composition for a thermal conductive material, obtained by curing the thermosetting resin composition for a thermal conductive material according to any one of [1] to [4] by heating. [6]: An electronic component comprising a cured product of the thermosetting resin composition for thermal conductive materials according to [5]. [7]: The electronic component according to [6], wherein the cured product is a circuit board or an insulating layer formed on a circuit board. [8]: The electronic component according to [6], wherein the cured product is used as an adhesive or a sealant. [9]: An electronic device equipped with the electronic component described in any one of [6] to [8]. Effect of the Invention

[0008] The present invention has an excellent effect of providing a highly reliable thermally conductive thermosetting resin composition having excellent thermal conductivity and dielectric properties, and a cured product thereof, an electronic component, and an electronic device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] An example of an embodiment to which the present invention is applied will be described below. The numerical values ​​specified in this specification are values ​​obtained by the method disclosed in the embodiment or example. The numerical values ​​"A to B" specified in this specification refer to a range that satisfies numerical value A and a value greater than numerical value A, and numerical value B and a value smaller than numerical value B. The sheet in this specification includes not only a sheet defined by JIS, but also a film. Unless otherwise noted, the various components appearing in this specification may be used independently, either alone or in combination of two or more.

[0010] The thermosetting resin composition for thermal conductive material of the present embodiment (hereinafter also referred to as "thermosetting resin composition") contains any one of the following binder components (I) to (IV) and a thermally conductive filler. The binder component (I) contains a styrene-based elastomer (P1) having a carboxylic acid anhydride group, and a polyisocyanate component (C1) that reacts with the anhydride group. The binder component (II) contains a polyamide resin (P2) having a phenolic hydroxyl group in a side group, and a trifunctional or higher compound (C2) that can react with the phenolic hydroxyl group. The binder component (III) contains a polyurethane resin (P3) having a carboxyl group, and an epoxy compound (C3) that can react with the carboxyl group. The binder component (IV) contains a polyimide resin (P4) having a reactive functional group and containing a hydrocarbon group having 20 to 60 carbon atoms, and a bifunctional or higher compound (C4) that can react with the reactive functional group. Furthermore, the thermosetting resin composition of this embodiment has a dielectric constant of 4.0 or less at a frequency of 5 GHz and 23°C, and a dielectric loss tangent of 0.010 or less at a frequency of 5 GHz and 23°C.

[0011] The thermosetting resin composition of the present embodiment has excellent thermal conductivity, and is therefore suitable for use in applications requiring thermal conductivity, particularly in applications requiring heat dissipation. The thermosetting resin composition of the present embodiment is melted by heating, and then hardened to exhibit adhesive properties, and can therefore be used as an adhesive material. In addition, by utilizing the moldability of the resin composition, it can be suitably used as a heat dissipation component of a desired shape. In particular, it is useful as a heat dissipation component for electronic devices (smartphones, tablet terminals, etc.) that cannot be equipped with fans or heat sinks due to their light, thin, short, and small size, and for battery exterior materials.

[0012] In addition, since the thermosetting resin composition of the present embodiment has excellent dielectric properties in addition to thermal conductivity, it is suitable for use as a circuit board itself or an insulating layer forming material on a circuit board (including a coverlay layer of a printed wiring board, an interlayer insulating layer such as a built-up board, a board forming material, a bonding sheet, etc.), a resin casting material such as an underfill material, a sealing material for a semiconductor chip, a material for forming an insulating layer of a semiconductor chip package, etc. It is also suitable as a bonding material between components such as an electronic circuit board and an electronic component. A suitable example of this bonding material is a bonding sheet. Since the binder component of the present embodiment has excellent electrical insulation, a cured product with excellent insulation can be provided by using a thermosetting resin composition that satisfies the relative dielectric constant and dielectric tangent of the present embodiment.

[0013] The thermosetting resin composition can be, for example, in the form of a powder, a film, a sheet, a plate, a pellet, a paste, or a liquid. The liquid or paste thermosetting resin composition can be easily obtained by adjusting the viscosity using a solvent. The film, sheet, or plate thermosetting resin composition can be formed, for example, by applying a liquid or paste thermosetting resin composition and drying it. The powder or pellet thermosetting resin composition can be obtained, for example, by pulverizing or cutting the film-like or other thermosetting resin composition into a desired size.

[0014] At the stage of the thermosetting resin composition, the thermosetting resin and the curing agent may have partially reacted, and the composition may be semi-cured (B-staged). The cured product of the thermosetting resin composition of the present embodiment can be obtained by curing the thermosetting resin composition by heating. Pressure may be applied during heating.

[0015] As described above, the dielectric constant of the cured product after curing the thermosetting resin composition of this embodiment is 4.0 or less at a frequency of 5 GHz and 23° C., and the dielectric loss tangent is 0.010 or less at a frequency of 5 GHz and 23° C. More preferably, the dielectric constant is 3.5 or less, the dielectric loss tangent is 0.005 or less, and even more preferably, the dielectric constant is 3.2 or less, and the dielectric loss tangent is 0.003 or less. The lower limit values ​​of the dielectric constant and the dielectric loss tangent are not particularly limited, but the dielectric constant is usually 2.0 or more, and the dielectric loss tangent is 0.001 or more. The dielectric constant and the dielectric loss tangent of the cured product of the thermosetting resin composition can be adjusted by the type of resin of the thermosetting resin composition and the type and amount of the filler.

[0016] The cured product of the thermosetting resin composition of the present embodiment is excellent in electrical insulation, thermal conductivity, and dielectric properties due to the combined use of the binder components (I) to (IV) and the thermally conductive filler, and is therefore particularly suitable for use as an insulating member for electronic components, such as semiconductor devices and circuit boards.

[0017] The semiconductor device is, for example, a power module such as a power semiconductor device, an LED, or an inverter device, and the semiconductor device is equipped with various heat generating elements such as semiconductor elements such as an insulated gate bipolar transistor, a diode, or an IC chip, a resistor, a capacitor, etc. The cured product of the thermosetting resin composition of the present embodiment is used for substrates, insulating layers, sealing materials, insulating layers of semiconductor chip packages, underfill materials, adhesives, etc. of semiconductor devices.

[0018] Examples of the circuit board include a printed wiring board, a laminate including a metal layer not classified as a printed wiring board, and an insulating resin layer. The cured product of the thermosetting resin composition of the present embodiment is preferably used, for example, as an insulating layer that is a constituent layer of a laminated board, or as a coverlay layer, a protective layer, or a bonding sheet for other members, parts, etc. of a printed wiring board. The cured product of the thermosetting resin composition of the present embodiment may be a cured product of a prepreg. In this case, the prepreg that is semi-cured by impregnating a substrate with the thermosetting resin composition of the present embodiment may be finally cured. A known material can be applied to the substrate.

[0019] The cured product of the thermosetting resin composition of the present embodiment is suitable as an adhesive layer between a heat generating body and a heat sink or as a heat spreader, and can also be used as a heat dissipation layer that covers one or more electronic components mounted on a substrate.

[0020] [Anisotropic conductive adhesive] The thermosetting resin composition of this embodiment can be used as an anisotropic conductive adhesive by further adding a conductive filler. The thermosetting resin composition using the binder component and the thermally conductive filler that satisfy the relative dielectric constant and dielectric properties of this embodiment and the anisotropic conductive adhesive further adding a conductive filler exhibits excellent thermal conductivity and excellent dielectric properties in the cured part of the thermosetting resin composition. Therefore, by using the anisotropic conductive adhesive of this embodiment in parts for high frequency applications, it is possible to exhibit better adhesive performance while maintaining good transmission properties.

[0021] For example, the anisotropic conductive adhesive can be used as a bonding layer for an electromagnetic shielding layer of a printed wiring board with an electromagnetic shielding layer. It can also be used as an anisotropic conductive connection film (for example, bonding between circuits, chip mounting, bonding between substrates, etc.) that replaces solder. According to the anisotropic conductive adhesive of this embodiment, the dielectric properties of the components of the cured product other than the conductive filler are excellent, so that the thermal conductivity and the transmission loss of signals in the high frequency band (MHz to GHz band) can be effectively suppressed. Thus, according to the anisotropic conductive adhesive of this embodiment, a material that exhibits anisotropic conductivity with excellent thermal conductivity and dielectric properties can be provided.

[0022] The anisotropic conductive adhesive can be used, for example, in the form of a film or sheet. Examples of the conductive filler include metal-based fillers. Examples of the metal filler include metal powders such as silver, copper, and nickel, alloy powders such as solder, silver-coated copper powder, gold-coated copper powder, silver-coated nickel powder, and gold-coated nickel powder. By containing silver, better conductivity can be obtained. Among these, silver-coated copper powder is particularly preferred from the viewpoint of cost. The coverage rate of the coating layer on the metal powder is preferably 80% or more on the surface.

[0023] In the case of coating a core in a conductive filler, the coating layer may cover at least a part of the core, but in order to obtain better conductive properties, a higher coverage is preferable. From the viewpoint of maintaining good conductive properties, the average coverage by the coating layer is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more.

[0024] <<Thermal conductive filler>> The thermally conductive filler used in this embodiment is a compound that imparts thermal conductivity to the cured product of the thermosetting resin composition for thermal conductive material of this embodiment. From the viewpoint of thermal conductivity, the thermally conductive filler preferably has a thermal conductivity of 10 W / m·K or more, more preferably 15 W / m·K or more, and even more preferably 20 W / m·K or more. As the thermally conductive filler, a thermally conductive inorganic filler or a thermally conductive organic-inorganic hybrid filler can be used.

[0025] Specific examples of thermally conductive inorganic fillers include metal oxides and metal nitrides such as alumina, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, calcium oxide, magnesium oxide, zinc oxide, beryllia, aluminum oxide, aluminum nitride, and boron nitride; hydrated metal compounds; silica-based fillers such as fused silica, crystalline silica, and amorphous silica; and nitride-based and carbon-based fillers such as silicon carbide, silicon nitride, titanium carbide, and diamond.

[0026] Among these, alumina, aluminum oxide, aluminum nitride, and boron nitride are more preferable, and alumina and boron nitride are particularly preferable from the viewpoints of heat resistance, thermal conductivity, and low dielectric constant. A combination of alumina and boron nitride is also suitable. When alumina and boron nitride are used in combination, the mass ratio of boron nitride / alumina is preferably in the range of 60 / 40 to 95 / 5, and more preferably 80 / 20 to 95 / 5. By setting the boron nitride / alumina in the range of 60 / 40 to 95 / 5, the effect of having excellent heat resistance, low dielectric constant, and thermal conductivity while also having excellent adhesiveness is obtained. The thermally conductive filler is used alone or in combination of multiple types.

[0027] Specific examples of the thermally conductive organic-inorganic hybrid filler include fillers in which the surface of the inorganic filler listed above is coated with a resin or a dispersant. A known method can be applied as a method for coating the surface of the thermally conductive inorganic filler with a resin or a dispersant. In this case, in order to effectively bring out the thermal conductive properties of the thermally conductive inorganic filler, it is preferable that the inorganic filler is exposed. The surface of the thermally conductive inorganic filler can be surface-treated with, for example, a silane-based, titanate-based, or aluminate-based coupling agent. The surface treatment can increase the dispersibility of the thermally conductive filler in the binder component. In addition, the interfacial adhesive strength between the binder component and the thermally conductive filler can also be increased.

[0028] Examples of silane coupling agents include aminosilanes such as γ-aminopropyltriethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, γ-aminopropyltrimethoxysilane, and γ-ureidopropyltriethoxysilane; epoxysilanes such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercaptosilanes such as 3-mercaptopropyltrimethoxysilane; and vinylsilanes such as p-styryltrimethoxysilane, vinyltrichlorosilane, vinyltris(β-methoxyethoxy)silane, vinyltrimethoxysilane, vinyltriethoxysilane, and γ-methacryloxypropyltrimethoxysilane.

[0029] Examples of titanate coupling agents include isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl aminoethyl) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, diisopropyl bis(dioctyl phosphate) titanate, tetraisopropyl bis(dioctyl phosphite) titanate, and tetraoctyl bis(ditridecyl phosphite) titanate.

[0030] In addition, a preferred embodiment is one in which the surface of the thermally conductive inorganic filler is coated with a fluorine-based resin. From the viewpoint of maintaining good thermal conductivity, it is preferred that the thermally conductive inorganic filler is exposed at the portion where the thermally conductive inorganic filler contacts each other.

[0031] From the viewpoint of more effectively achieving a low dielectric constant, a mode in which a thermally conductive inorganic filler is used in combination with a fluorine-based filler is also suitable. Examples of fluorine-based fillers include PTFE, PVDF (vinylidene fluoride polymer having a linear structure in which CF2 and CH2 are alternately bonded), NEOFLON FEP (tetrafluoroethylene-hexafluoropropylene copolymer: tetrafluoroethylene-hexafluoropropylene copolymer resin), PFA (tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer: perfluoroalkoxy resin), NEOFLON ETFE (tetrafluoroethylene and ethylene copolymer), and ECTFE (polychlorotrifluoroethylene: trifluorochloroethylene resin). Among these, a combination of a polytetrafluoroethylene PTFE filler and a thermally conductive filler, particularly a thermally conductive inorganic filler, is preferred.

[0032] The fluorine-based filler may contain fillers such as glass fiber, carbon fiber, graphite, bronze, molybdenum disulfide, and carbon.

[0033] The preferred range of the average particle size (D50) of the thermally conductive filler calculated by the laser diffraction scattering method may vary depending on the application, but may be, for example, 0.1 to 250 μm. Nano-order particles and micro-order particles may be used in combination. Examples of particle shapes include spherical, needle-like, flake-like, dendritic, and fibrous shapes. By using multiple types of thermally conductive fillers with different particle sizes and shapes, it may be possible to highly fill the thermally conductive filler.

[0034] The content of the thermally conductive filler in the thermosetting resin composition can be appropriately adjusted depending on the application. From the viewpoint of the balance between thermal conductivity, adhesive properties, and flexibility, it is preferable to set the range of the thermally conductive filler to 30 to 500 parts by mass per 100 parts by mass of the thermosetting resin.

[0035] <<Binder components>> Preferred embodiments of the binder components (I) to (IV) will be described below.

[0036] [[Binder component (I)]] The binder component (I) contains a styrene-based elastomer (P1) having a carboxylic acid anhydride group (hereinafter sometimes abbreviated as an acid anhydride group) and a polyisocyanate component (C1) that reacts with the acid anhydride group. In this specification, the term "elastomer" refers to a polymer that has rubber elasticity at room temperature even without vulcanization treatment. In terms of chemical structure, it generally has an ABA type block or an (AB)n type multiblock structure. In addition, the styrene-based elastomer refers to a copolymer having a block containing polystyrene (hereinafter also referred to as a polystyrene block).

[0037] <Styrene-based elastomer (P1)> It is important that the styrene-based elastomer (P1) has an anhydride group of a carboxylic acid. By reacting the acid anhydride group in the styrene-based elastomer (P1) with the polyisocyanate component (C1) described later, an imide group that has excellent heat resistance and a function of suppressing the dielectric constant and the dielectric loss tangent to a low level can be formed. A preferred example of the styrene-based elastomer (P1) is a block copolymer having at least one of a structural unit derived from an olefin and a structural unit derived from a conjugated diene, and a structural unit derived from styrene. By using the styrene-based elastomer (P1) having a polystyrene structure in the molecule, excellent heat resistance can be realized. Specific examples include styrene-butadiene block copolymers, styrene-ethylene-propylene block copolymers, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-ethylene-butylene-styrene block copolymers, styrene-ethylene-propylene block copolymers, and styrene-isoprene-styrene block copolymers. In these styrene-based elastomers (P1), the portions other than the polystyrene blocks are regarded as one block. In addition, among the portions other than the polystyrene blocks, examples of blocks formed from units (residues) derived from two or more monomers include, in the above example, a copolymer of ethylene and propylene and a copolymer of ethylene and butylene. Such blocks formed from units derived from two or more monomers other than the polystyrene blocks may be random copolymers or block copolymers.

[0038] Imide groups can also be formed by the reaction of an acid anhydride group with an amino group, but this is not preferred for the following reasons. The first-stage reaction between an acid anhydride group and an amino group, i.e., the ring-opening reaction of an acid anhydride group by an amino group, is extremely fast, and this causes a problem that the usable time of the thermosetting adhesive is shortened. The second-stage reaction between an acid anhydride group and an amino group, i.e., the reaction of forming an imide group by ring-closing an amic acid, requires higher heating temperature than the reaction of forming an imide group by the reaction of an acid anhydride group with an isocyanate group. If the heating is insufficient, the amic acid, which is the precursor of the imide group, remains, and the dielectric constant and dielectric tangent become high. In addition, if the amic acid remains, when the thermosetting resin is cured, the imidization reaction accompanied by the elimination of water may proceed explosively, causing foaming. When the carboxylic anhydride group and the isocyanate group are heat-cured at about 150 to 200°C, the heat resistance and insulating properties are improved, the dielectric constant and the dielectric loss tangent are lowered, and the 1700 cm peak in the infrared absorption spectrum is obtained, as in the case of the reaction between the carboxylic anhydride group and the amino group. -2 Since a new peak was observed in the vicinity, it is considered that an imide group was formed.

[0039] Examples of methods for introducing an acid anhydride group into the styrene-based elastomer (P1) include a method of polymerizing a monomer having an acid anhydride group as one of the raw materials for producing the styrene-based elastomer (P1) with other raw materials, a method of introducing an acid anhydride group into a side chain after polymer synthesis, and a method of grafting reaction. For example, a method of copolymerizing an appropriate amount of an ethylenically unsaturated carboxylic acid anhydride such as maleic anhydride, and a method of synthesizing the styrene-based elastomer (P1) and then grafting using an appropriate amount of an ethylenically unsaturated carboxylic acid anhydride such as maleic anhydride and a peroxide can be mentioned. Also, instead of an acid anhydride, an appropriate amount of an ethylenically unsaturated carboxylic acid such as maleic acid can be used. In this case, at least a part of the carboxylic acid is made to be an anhydride group after the introduction of the carboxylic acid.

[0040] The styrene-based elastomer (P1) preferably contains 5 to 60% by mass of polystyrene blocks, more preferably 10 to 50% by mass, and even more preferably 20 to 40% by mass, based on 100% by mass excluding the anhydride of an ethylenically unsaturated carboxylic acid. When the polystyrene block content is 5% by mass or more, a cured product with excellent viscoelasticity is obtained, and when the polystyrene block content is 60% by mass or less, solubility in solvents is improved, and the solution stability of the thermosetting resin composition is excellent.

[0041] The acid anhydride value of the styrene-based elastomer (P1) is preferably 0.1 to 40 mgCH3ONa / g, more preferably 1 to 30 mgCH3ONa / g, and even more preferably 5 to 20 mgCH3ONa / g. By using a styrene-based elastomer (P1) having an acid anhydride value of 0.1 mgCH3ONa / g or more, the adhesiveness can be improved, and the heat resistance and insulating properties can be improved. By using a styrene-based elastomer (P1) having an acid anhydride value of 40 mgCH3ONa / g or less, a low dielectric constant necessary for printed wiring boards through which high-frequency electric signals propagate can be achieved.

[0042] In addition, styrene-based elastomers (P1) in which some of the acid anhydride groups have been ring-opened by water, alcohol, amine, etc. to become carboxylic acids can also be used as styrene-based elastomers (P1). By opening some of the acid anhydride groups to become carboxylic acids, it is expected that the adhesive strength to conductive circuits described below will be improved. However, if all of the acid anhydride groups are ring-opened to become carboxylic acids, amide groups will be generated instead of imide groups upon reaction with the polyisocyanate component (C1) described below, resulting in a large dielectric tangent.

[0043] The ratio of the acid anhydride to the ring-opened carboxylic acid is preferably 100-50:0-50, more preferably 100-75:0-25, and further preferably 100-85:0-15, in terms of molar ratio. The ratio of the acid anhydride group to the ring-opened carboxylic acid can be determined by the following method. That is, the amount (mg) of sodium methoxide required to neutralize 1 g of the styrene-based elastomer (P1) is determined, and this is taken as the total acid value. The amount of carboxylic acid contained in 1 g of the styrene-based elastomer (P1): X (mmol) is determined by dividing the total acid value by the molecular weight of sodium methoxide. The total acid value includes both the carboxylic acid whose acid anhydride group contained in 1 g of the styrene-based elastomer (P1) has been ring-opened at the time of measuring the acid value, and the carboxylic acid that has already been ring-opened at the time of measuring the acid value. Separately, the amount of perchloric acid (mmol) required to neutralize 1 g of styrene-based elastomer (P1) is calculated, and this is converted into the amount of sodium methoxide (mg) to obtain the acid anhydride value. The amount of acid anhydride groups Y (mmol) contained in 1 g of styrene-based elastomer (P1) can be calculated by dividing the acid anhydride value by the molecular weight of sodium methoxide. When 1 mole of an acid anhydride group opens, it becomes 2 moles of carboxylic acid. If the amount of carboxylic acid that is contained in 1 g of styrene-based elastomer (P1) and has already opened at the time of measuring the acid value is Z (mmol), then: Z=X-2Y. In other words, the ratio of acid anhydride and ring-opened carboxylic acid contained in the styrene-based elastomer (P1) is: Y:Z=Y:(X-2Y). The molecular weight of sodium methoxide, which is the standard for the total acid value, and the molecular weight of potassium hydroxide, which is the standard for the acid anhydride value, are close in value. Therefore, if the total acid value is X', the acid anhydride value is Y', and the acid value derived from the carboxylic acid that had already been opened at the time of measuring the acid value is Z', then In simple terms, Z'=X'-2Y', The ratio of acid anhydride and ring-opened carboxylic acid contained in the styrene-based elastomer (P1) is: It can be expressed as Y':Z'=Y':(X'-2Y').

[0044] The styrene-based elastomer (P1) preferably has a mass average molecular weight of about 5,000 to 1,000,000, more preferably 10,000 to 500,000, still more preferably 25,000 to 200,000, and still more preferably 25,000 to 100,000.

[0045] Commercially available styrene-based elastomers (P1) include, for example, the Tuftec M series manufactured by Asahi Kasei Corporation and the Kraton FG series manufactured by Kraton Polymer Japan Co., Ltd. These may be used alone or in combination of two or more kinds.

[0046] <Polyisocyanate component (C1)> By reacting the polyisocyanate component (C1) with the above-mentioned styrene-based elastomer (P1), a cured product having excellent heat resistance and insulating properties, and low dielectric constant and dielectric loss tangent can be obtained. The polyisocyanate component (C1) is preferably an isocyanate group-containing compound having two or more isocyanates. Furthermore, it can also impart adhesiveness. The isocyanate compound is not particularly limited as long as it has two or more isocyanate groups in the molecule.

[0047] Specific examples of isocyanate group-containing compounds having two isocyanate groups in one molecule include aromatic diisocyanates such as 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, dianisidine diisocyanate, and 4,4'-diphenyl ether diisocyanate; Aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate; Aromatic aliphatic diisocyanates such as ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate; Examples of alicyclic diisocyanates include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate [also known as isophorone diisocyanate], 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,3-bis(isocyanatemethyl)cyclohexane, and 1,4-bis(isocyanatemethyl)cyclohexane.

[0048] Specific examples of the isocyanate group-containing compound having three isocyanate groups in one molecule include aromatic polyisocyanates such as 2,4,6-triisocyanate toluene and 1,3,5-triisocyanate benzene, aliphatic polyisocyanates such as lysine triisocyanate, aromatic aliphatic polyisocyanates such as 4,4',4"-triphenylmethane triisocyanate, and alicyclic polyisocyanates, as well as the above-described trimethylolpropane adduct of diisocyanate, biuret product reacted with water, and trimers having an isocyanurate ring.

[0049] A blocked isocyanate in which at least a part of the isocyanate groups of the polyisocyanate component (C1) is blocked with a blocking agent may be used. Specific examples include polyisocyanate components (C1) in which the isocyanate groups are blocked with ε-caprolactam, MEK (methyl ethyl ketone) oxime, cyclohexanone oxime, pyrazole, phenol, etc. In particular, the use of a hexamethylene diisocyanate trimer having an isocyanurate ring and blocked with MEK oxime or pyrazole is highly preferred because it enhances the adhesive strength to polyimide and copper and has excellent heat resistance.

[0050] The content of isocyanate groups in the polyisocyanate component (C1) relative to 1 mol of acid anhydride groups in the styrene-based elastomer (P1) is preferably in the range of 0.1 to 20 mol, more preferably in the range of 0.5 to 10 mol, and even more preferably in the range of 1 to 3 mol. By making the content of isocyanate groups 0.1 mol or more relative to the acid anhydride groups in the styrene-based elastomer (P1), the crosslink density can be increased and the heat resistance, insulating properties, and adhesiveness can be improved. By making the content of isocyanate groups 20 mol or less, the generation of new polar groups can be suppressed, and the decrease in dielectric tangent can be suppressed.

[0051] <Silane coupling agents, thiol compounds> The thermosetting resin composition using the binder component (I) can contain a silane coupling agent and / or a thiol compound within a range that does not impair the physical properties. By reacting the silane coupling agent and / or the thiol compound with, for example, a styrene-based elastomer (P1), a cured product having excellent heat resistance and insulation properties and low dielectric constant and dielectric loss tangent can be obtained. Furthermore, adhesiveness can also be imparted. In addition, by using the silane coupling agent and the thiol compound, the adhesiveness to conductive patterns, conductive layers, and resin films, typified by copper, can be improved. In addition, the solder heat resistance after humidification, the flexibility of the cured product of the thermosetting resin composition, and the electrical insulation can be improved without deteriorating the dielectric constant and dielectric loss tangent.

[0052] Examples of the silane coupling agent include silane coupling agents having N, S or O and / or their hydrolysis condensates. For example, vinyl methoxy silane, vinyl ethoxy silane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxy silane, 3-glycidoxypropyl methyl dimethoxy silane, 3-glycidoxypropyl trimethoxy silane, 3-glycidoxypropyl methyl diethoxy silane, 3-glycidoxypropyl triethoxy silane, p-styryl trimethoxy silane, 3-methacryloxypropyl methyl dimethoxy silane, 3-methacryloxypropyl triethoxy silane, 3-acryloxypropyl trimethoxy silane, N-2-(aminoethyl)-3-aminopropyl methyl dimethoxy silane, N-2-(aminoethyl)-3-aminopropyl trimethoxy silane, 3-aminopropyl trimethoxy silane, 3-aminopropyl triethoxy silane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene In addition to 1,2-ethanediamine, N-{3-(trimethoxysilyl)propyl}-, N-{(ethenylphenyl)methyl} derivatives·hydrochloride, vinyltriacetoxysilane, and allyltrimethoxysilane, silane coupling agents in which the functional group is protected with an alkoxy group, sulfide / polysulfide silane coupling agents, polymer-type alkoxy oligomer type, and multifunctional group type silane coupling agents can be used.

[0053] The thiol compound contains, for example, at least a thiol group and a linear or branched chain hydrocarbon group or a cyclic hydrocarbon group. It may contain two or more thiol groups. The hydrocarbon group may be saturated or unsaturated. Some of the hydrogen atoms of the hydrocarbon group may be substituted with a hydroxyl group, an amino group, a carboxyl group, a halogen atom, an alkoxysilyl group, or the like. Examples of colorless thiols include 1-propanethiol, 3-mercaptopropionic acid, (3-mercaptopropyl)trimethoxysilane, 1-butanethiol, 2-butanethiol, isobutyl mercaptan, isoamyl mercaptan, cyclopentanethiol, 1-hexanethiol, cyclohexanethiol, 6-hydroxy-1-hexanethiol, 6-amino-1-hexanethiol hydrochloride, 1-heptanethiol, 7-carboxy-1-heptanethiol, 7-amido-1-heptanethiol, 1-octanethiol, tert-octanethiol, 8-hydroxy-1-octanethiol, 8-amino-1-octanethiol hydrochloride, 1H,1H,2H,2H-perfluorooctanethiol, 1-nonanethiol, 1-decanethiol, 10-carboxy-1 -decanethiol, 10-amido-1-decanethiol, 1-naphthalenethiol, 2-naphthalenethiol, 1-undecanethiol, 11-amino-1-undecanethiol hydrochloride, 11-hydroxy-1-undecanethiol, 1-dodecanethiol, 1-tetradecanethiol, 1-hexadecanethiol, 16-hydroxy-1-hexadecanethiol, 16-amino-1-hexadecanethiol hydrochloride, 1-octadecanethiol, 1,4-butanedithiol, 2,3-butanedithiol, 1,6-hexaneedithiol, 1,2-benzeneedithiol, 1,9-nonanedithiol, 1,10-decanedithiol, 1,3,5-benzenetrithiol, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, etc. The thiols can be used alone or in combination of two or more.

[0054] The amount of the silane coupling agent and / or thiol compound contained in the thermosetting resin composition containing the binder component (I) is not particularly limited, but is preferably 0.01 to 50 parts by mass in total, more preferably 0.1 to 25 parts by mass, and even more preferably 1 to 15 parts by mass, based on 100 parts by mass of the solid content of the styrene-based elastomer (P1). By containing a thiol compound or a silane coupling agent (not containing a sulfur atom), when the thermosetting resin composition is cured, in addition to improving the dimensional stability and improving the heat resistance of the cured product after humidification, it is possible to improve the performance, which is easily contradictory, of achieving both adhesiveness and low dielectric constant and electrical insulation in a more balanced manner.

[0055] The thermosetting resin composition containing the binder component (I) may further contain a filler for the purpose of imparting flame retardancy, etc. For example, polymer fillers such as polytetrafluoroethylene powder, polyethylene powder, polyacrylic ester powder, epoxy resin powder, polyamide powder, polyurethane powder, polysiloxane powder, etc., as well as multi-layered core-shell fillers using silicone, acrylic, styrene-butadiene rubber, butadiene rubber, etc.; (Poly)phosphate compounds such as melamine phosphate, melamine polyphosphate, guanidine phosphate, guanidine polyphosphate, ammonium phosphate, ammonium polyphosphate, ammonium amido phosphate, ammonium amido polyphosphate, carbamate phosphate, and carbamate polyphosphate, organic phosphate ester compounds, phosphazene compounds, phosphonic acid compounds, phosphinic acid compounds such as aluminum diethylphosphinate, aluminum methylethylphosphinate, aluminum diphenylphosphinate, aluminum ethylbutylphosphinate, aluminum methylbutylphosphinate, and aluminum polyethylenephosphinate, phosphine oxide compounds, phosphorus-based flame-retardant fillers such as phosphorus oxide compounds, phosphorane compounds, and phosphoramide compounds; Nitrogen-based flame-retardant fillers such as benzoguanamine, melamine, melam, melem, melon, melamine cyanurate, cyanuric acid compounds, isocyanuric acid compounds, triazole compounds, tetrazole compounds, diazo compounds, and urea; Examples of inorganic fillers include silica, mica, talc, kaolin, clay, hydrotalcite, wollastonite, xonotlite, calcium hydrogen phosphate, calcium phosphate, glass flakes, hydrated glass, calcium titanate, sepiolite, magnesium sulfate, zirconium hydroxide, barium hydroxide, calcium hydroxide, titanium oxide, tin oxide, zirconium oxide, molybdenum oxide, antimony oxide, nickel oxide, zinc carbonate, barium carbonate, zinc borate, and aluminum borate.

[0056] Considering the environmental impact that has been discussed in recent years, it is desirable to use a non-halogen flame retardant such as a phosphorus-based flame retardant filler or a nitrogen-based flame retardant filler. Among them, examples of fillers that are more effective in flame retardancy when used in combination with the binder component (I) include phosphazene compounds, phosphine compounds, melamine polyphosphate, ammonium polyphosphate, melamine cyanurate, and hydroxide compounds. In addition, in terms of further reducing the dielectric constant and dielectric loss tangent, it is preferable to use polytetrafluoroethylene powder and phosphine compounds, and it becomes possible to obtain a cured product that is excellent in balance not only in dielectric properties but also in adhesion, flexibility, electrical insulation, and heat resistance. The fillers are used alone or in combination.

[0057] The total content of the fillers may be, for example, 0.01 to 500 parts by mass per 100 parts by mass of the styrene-based elastomer (P1). The fillers can improve the modifying effect and the mechanical properties of the cured product.

[0058] The filler (including thermally conductive filler) can be added by any conventional method without any restrictions. For example, a dispersion containing the filler is prepared, and the dispersion containing the filler is kneaded with a reaction liquid before, during, or after the polymerization of the styrene-based elastomer (P1) using a three-roll mill or the like. In order to disperse the filler well and stabilize the dispersion state, a dispersant and / or a thickener may be used within a range that does not affect the properties.

[0059] <Other ingredients> In addition to the essential components and the optional components described above, the binder component (I) may further contain, within the scope of the purpose, an epoxy group-containing compound, an oxetane group-containing compound, an aziridine group-containing compound, a carbodiimide group-containing compound, a benzoxazine compound, a β-hydroxyalkylamide group-containing compound, etc. Also, it may contain dyes, pigments, antioxidants, polymerization inhibitors, defoamers, leveling agents, ion collectors, moisturizers, viscosity adjusters, preservatives, antibacterial agents, antistatic agents, antiblocking agents, ultraviolet absorbers, infrared absorbers, etc.

[0060] Examples of the epoxy group-containing compound include epoxy resins such as glycidyl ether type epoxy resins, glycidyl amine type epoxy resins, glycidyl ester type epoxy resins, and cyclic aliphatic (alicyclic) epoxy resins. Examples of the glycidyl ether type epoxy resins include cresol novolac type epoxy resins, phenol novolac type epoxy resins, α-naphthol novolac type epoxy resins, bisphenol A type novolac type epoxy resins, tetrabromo bisphenol A type epoxy resins, brominated phenol novolac type epoxy resins, tris(glycidyloxyphenyl)methane, or tetrakis(glycidyloxyphenyl)ethane. Examples of the glycidyl amine type epoxy resins include tetraglycidyl diamino diphenyl methane, triglycidyl para aminophenol, triglycidyl meta aminophenol, or tetraglycidyl meta xylylene diamine. Although examples of the oxetane group-containing compound, aziridine compound, carbodiimide group-containing compound, benzoxazine compound, and β-hydroxyalkylamide group-containing compound are omitted, known compounds can be appropriately selected and used.

[0061] [[Binder component (II)]] The binder component (II) contains a polyamide resin (P2) (hereinafter also referred to as "polyamide resin (P2)") having a phenolic hydroxyl group in a side group, and a tri- or higher functional compound (C2) (hereinafter also referred to as "compound (C2)") capable of reacting with the above-mentioned phenolic hydroxyl group.

[0062] <Polyamide resin (P2)> The polyamide resin (P2) is usually synthesized using a polybasic acid compound selected from divalent or higher polybasic acids and / or acid anhydrides and / or lower alkyl esters thereof as monomers, and a divalent or higher polyamine compound. The phenolic hydroxyl groups in the polyamide resin (P2) can form a crosslinked structure by thermal curing with a trifunctional or higher compound (C2). Suitable examples of the polyamide resin (P2) include the following (i) and / or (ii). That is, the polyamide (P2) of (i) is a polyamide (A-1) in which a phenolic hydroxyl group and a hydrocarbon group having 20 to 60 carbon atoms (but not including an aromatic ring to which the phenolic hydroxyl group is bonded) are contained in the same polymer. The polyamide (P2) of (ii) is a polyamide (A-3) obtained by mixing a polyamide (a-1) containing a phenolic hydroxyl group in a side group with a polyamide (a-2) containing a hydrocarbon group having 20 to 60 carbon atoms (but not including an aromatic ring to which the phenolic hydroxyl group is bonded).

[0063] From the viewpoints of solubility in general-purpose solvents and productivity, the former polyamide (A-1) is preferred. In the following description, the parentheses for the hydrocarbon group having 20 to 60 carbon atoms (excluding the aromatic ring to which the phenolic hydroxyl group is bonded) are omitted, but when the term "hydrocarbon group having 20 to 60 carbon atoms" is used, the term "hydrocarbon group having 20 to 60 carbon atoms" satisfies the above-mentioned parenthetical conditions. The term "hydrocarbon group having 20 to 60 carbon atoms" is also written as "C20 to 60 hydrocarbon group". The term "hydrocarbon group having 20 to 60 carbon atoms" refers to a hydrocarbon group having 20 to 60 carbon atoms contained in all or part of the residues other than the functional groups that contribute to the polymerization of the monomer, and the number of carbon atoms in a continuous structure that does not contain elements other than carbon and hydrogen is counted. More preferably, all of the residues other than the functional groups that contribute to the polymerization of the monomer are hydrocarbon groups having 20 to 60 carbon atoms. That is, it refers to the total number of carbon atoms in the continuous hydrocarbon groups, including the main chain and the side groups or side chains directly connected to the main chain, in the obtained polyamide (A-1), and includes aliphatic (including alicyclic) and aromatic rings. However, it does not include aromatic rings to which phenolic hydroxyl groups are bonded. In addition, each of the hydrocarbon groups bonded via aromatic rings to which phenolic hydroxyl groups are bonded is counted as a separate hydrocarbon group.

[0064] Further, suitable examples of the polyamide resin (P2) of (i) include polyamide resins satisfying the following (iii) and (vi), and suitable examples of the polyamide resin (P2) of (ii) include polyamide resins satisfying (iv) to (vi). (iii) Monomers constituting the polyamide (A-1) include a monomer having a phenolic hydroxyl group and a monomer having a hydrocarbon group having 20 to 60 carbon atoms. It goes without saying that a monomer having a phenolic hydroxyl group and a hydrocarbon group having 20 to 60 carbon atoms may be used within the same type of monomer. (iv) The polybasic acid monomer and / or polyamine monomer constituting the polyamide (a-1) contains a monomer having a phenolic hydroxyl group, and the polybasic acid monomer and the polyamine monomer do not contain a monomer having a hydrocarbon group having 20 to 60 carbon atoms. (v) The polybasic acid monomer and / or polyamine monomer constituting the polyamide (a-2) contains a monomer having a hydrocarbon group having 20 to 60 carbon atoms, and the polybasic acid monomer and the polyamine monomer do not contain a monomer having a phenolic hydroxyl group. (vi) The monomer having a hydrocarbon group with 20 to 60 carbon atoms includes a compound having a cyclic structure with 5 to 10 carbon atoms. Note that "including a compound having a cyclic structure with 5 to 10 carbon atoms" means that at least a part of the monomer having a hydrocarbon group with 20 to 60 carbon atoms includes a monomer having a cyclic structure with 5 to 10 carbon atoms.

[0065] Of the monomers having a hydrocarbon group with 20 to 60 carbon atoms, from the viewpoint of effectively bringing out solubility and flexibility, a monomer having a hydrocarbon group with 24 to 56 carbon atoms is more preferable, a monomer having a hydrocarbon group with 28 to 48 carbon atoms is even more preferable, and a monomer having a hydrocarbon group with 36 to 44 carbon atoms is even more preferable.

[0066] By using the polyamide resin (P2), it is possible to provide a cured product of the thermosetting resin composition that is excellent in moisture and heat resistance and flexibility without impairing heat resistance and chemical resistance. In addition, there is also an advantage that it is possible to provide a thermosetting resin composition that can be used in a wide range of general-purpose organic solvents. In addition, by using the binder component (II) and the thermally conductive filler, it is possible to obtain excellent electrical insulation and thermal conductivity, and to significantly improve the dielectric constant and dielectric loss tangent of high-frequency circuits, such as printed wiring boards through which high-frequency electrical signals propagate. In addition, it is possible to obtain adhesion to metals such as copper and polyimide substrates, heat resistance during solder reflow, and flexibility when folding a circuit board (metal-clad laminate, printed wiring board, etc.) containing a cured product of the thermosetting resin composition.

[0067] By using a monomer having a phenolic hydroxyl group as a monomer constituting the polyamide resin (P2) and introducing a functional group (phenolic hydroxyl group) that serves as a crosslinking point into the side group of the main chain skeleton, the crosslink density by thermal curing can be increased and heat resistance during solder reflow can be imparted. As for the phenolic hydroxyl group of the side group, a polybasic acid compound (polybasic acid monomer) having a phenolic hydroxyl group and / or a polyamine compound (polyamine monomer) having a phenolic hydroxyl group can be used as the raw material of the polyamide resin (P2) as described later. In addition, by introducing a C20-60 hydrocarbon group into the polyamide resin (P2), the concentration of amide bonds with high water absorption can be relatively lowered, thereby improving insulation reliability and dielectric properties. Furthermore, due to the flexibility inherent to the C20-60 hydrocarbon group, and by introducing a phenolic hydroxyl group into the monomer constituting the polyamide resin (P2), flexibility can be improved. Therefore, the thermosetting resin composition containing the binder component (II) can be suitably used as an insulating layer such as a coverlay layer for a printed wiring board or the like that requires foldability.

[0068] By including a compound having a cyclic structure with 5 to 10 carbon atoms as a monomer having a C20-60 hydrocarbon group in the polyamide resin (P2), the molecular arrangement can be hindered and the crystallinity can be reduced. As a result, the solubility can be improved. In addition, since the compound having a cyclic structure with 5 to 10 carbon atoms has a structure containing a hydrocarbon group such as a chain-like alkyl group having high freedom and hydrophobicity in a portion other than the cyclic structure, it is possible to more effectively increase the solubility and effectively reduce the dielectric constant and the dielectric loss tangent. The C20-60 hydrocarbon group can be introduced by using a polybasic acid compound having a C20-60 hydrocarbon group and / or a polyamine compound having a C20-60 hydrocarbon group as a raw material for the polyamide resin (P2) as described later.

[0069] Since the polyamide resin (P2) has two structures, a phenolic hydroxyl group and a C20-60 hydrocarbon group, it can be dissolved in a general-purpose organic solvent, and when used in combination with a thermally conductive filler, it has excellent thermal conductivity, can reduce the dielectric constant and dielectric tangent, and can solve the trade-off between adhesiveness and heat resistance, and flexibility and electrical insulation. Preferred embodiments of the polyamides (A-1) and (A-3) are described in detail below.

[0070] <Polyamide (A-1)> The polyamide (A-1) is obtained by polymerizing a polybasic acid monomer (m1) and a polyamine monomer (m2), has a phenolic hydroxyl group on a side group, and has a phenolic hydroxyl group and a C20-60 hydrocarbon group in the same polymer. That is, the polybasic acid monomer (m1) is selected from at least one selected from the group consisting of a polybasic acid compound having a phenolic hydroxyl group, a polybasic acid compound containing a C20-60 hydrocarbon group, and other polybasic acid compounds, and the polyamine monomer (m2) is selected from at least one selected from the group consisting of a polyamine compound having a phenolic hydroxyl group, a polyamine compound containing a C20-60 hydrocarbon group, and other polyamine compounds, so that the polymer contains a phenolic hydroxyl group and a C20-60 hydrocarbon group. The polyamide (A-1) can be obtained by polymerizing a polybasic acid monomer (m1) and a polyamine monomer (m2) selected so that the compound containing a C20-60 hydrocarbon group and the compound containing a phenolic hydroxyl group are contained in the same type of monomer or in a different monomer.

[0071] Here, "so as to be included in the same type of monomer" means that a polybasic acid compound having a phenolic hydroxyl group and a polybasic acid compound having a C20-60 hydrocarbon group may be used as the polybasic acid monomer (m1), or a polyamine compound having a phenolic hydroxyl group and a polyamine compound having a C20-60 hydrocarbon group may be used as the polyamine monomer (m2). Also, "so as to be included in another monomer" means that a polybasic acid compound having a phenolic hydroxyl group may be included as the polybasic acid monomer (m1) and a polyamine compound having a C20-60 hydrocarbon group may be included as the polyamine monomer (m2), or a polybasic acid compound having a C20-60 hydrocarbon group may be included as the polybasic acid monomer (m1) and a polyamine compound having a phenolic hydroxyl group may be included as the polyamine monomer (m2). In either case, other polybasic acid compounds and other polyamine compounds may be used as appropriate.

[0072] The phenolic hydroxyl group introduced into the side group functions as a crosslinking point for the main chain formed by polymerization of the polybasic acid monomer (m1) and the polyamine monomer (m2). That is, a dense crosslinked structure can be formed by thermally curing the polyamide (A-1) with the trifunctional or higher compound (C2) that can react with the phenolic hydroxyl group described later. As a result, the heat resistance during soldering after thermal curing is also improved.

[0073] In addition, the C20-60 hydrocarbon group reduces the concentration of highly hygroscopic amide bonds and also provides and improves flexibility and bendability. This reduces the hygroscopicity of the cured product after heat curing, improves its resistance to moisture and heat, and achieves a low dielectric constant and low dielectric loss tangent, which are important factors for printed wiring boards and other devices that transmit high-frequency electrical signals.

[0074] The polybasic acid compound as the polybasic acid monomer (m1) and the polyamine compound as the polyamine monomer (m2) may be divalent or higher monomers, and trivalent or higher monomers may be used as appropriate. A divalent monomer and a trivalent or higher monomer may be combined to introduce a branched structure and adjust the molecular weight appropriately. It is also possible to use a monovalent monomer to keep the molecular weight appropriate. By partially including a trivalent or higher monomer, the effect of increasing the cohesive force can be obtained. The trivalent or higher monomer is preferably 0.1 to 20 mol % of the total monomers, and more preferably 1 to 10 mol % or less.

[0075] When the polyamide resin (P2) is obtained using a dibasic acid monomer and a diamine monomer, it has a structural unit of the following general formula (1). [ka] In the general formula (1), R1 is a divalent linking group which is a polybasic acid compound residue which may have an independent structure for each structural unit, and R2 is a divalent linking group which is a polyamine compound residue which may have an independent structure for each structural unit, and at least one of R1 and R2 includes a linking group having a phenolic hydroxyl group, and at least one of R1 and R2 includes a linking group having a C20-60 hydrocarbon group. The polyamide (A-1) is a compound in which at least two structural units represented by -CO-R1-CO-NH-R2-NH- are repeated. Note that, within the scope of the present embodiment, a compound having one structural unit of the general formula (1) and having a blocked end may be included in the thermosetting resin composition.

[0076] The phenolic hydroxyl group-containing monomer and the C20-60 hydrocarbon group-containing monomer may be contained in at least one of the dibasic acid compound and the diamine compound, and these groups may be contained in both the dibasic acid compound and the diamine compound. For example, two kinds of dibasic acid compounds R 1-1 , R 1-2 and two diamine compounds R 2-1 , R 2-2 When using -CO-R1-1 -CO-NH-R 2-1 -NH-, -CO-R 1-1 -CO-NH-R 2-2 -NH-, -CO-R 1-2 -CO-NH-R 2-1 -NH-, -CO-R 1-2 -CO-NH-R 2-2 It may contain -NH- structural units.

[0077] <Polybasic acid monomer (m1)> [Polybasic acid compounds having phenolic hydroxyl groups] The polybasic acid compound having a phenolic hydroxyl group is not particularly limited, and examples thereof include hydroxyisophthalic acids such as 2-hydroxyisophthalic acid, 4-hydroxyisophthalic acid, and 5-hydroxyisophthalic acid, dihydroxyisophthalic acids such as 2,5-dihydroxyisophthalic acid, 2,4-dihydroxyisophthalic acid, and 4,6-dihydroxyisophthalic acid, dihydroxyterephthalic acids such as 2-hydroxyterephthalic acid, 2,3-dihydroxyterephthalic acid, and 2,6-dihydroxyterephthalic acid, hydroxyphthalic acids such as 4-hydroxyphthalic acid and 3-hydroxyphthalic acid, and dihydroxyphthalic acids such as 3,4-dihydroxyphthalic acid, 3,5-dihydroxyphthalic acid, 4,5-dihydroxyphthalic acid, and 3,6-dihydroxyphthalic acid. In addition, examples thereof include acid anhydrides and ester derivatives such as polybasic acid methyl esters. The only difference is that in the case of free polybasic acids and acid anhydrides, a dehydration reaction occurs, while in the case of ester derivatives, a corresponding dealcoholization reaction occurs. Among these, 5-hydroxyisophthalic acid is preferred from the viewpoints of copolymerizability, availability, etc. When 5-hydroxyisophthalic acid is used, R1 in general formula (1), i.e., the divalent linking group which is a polybasic acid compound residue, is a portion obtained by removing two carboxyl groups from the 5-hydroxyisophthalic acid.

[0078] [Polybasic acid compounds containing C20-60 hydrocarbon groups] A suitable example of a polybasic acid compound containing a C20-60 hydrocarbon group is a polybasic acid compound having a cyclic structure with 5 to 10 carbon atoms, which is obtained by reacting a monobasic unsaturated fatty acid having one or more double or triple bonds with 10 to 24 carbon atoms. An example of the reaction is the Diels-Alder reaction. For example, a polybasic acid compound containing a dimerized fatty acid (dimer acid) obtained by subjecting natural fatty acids such as soybean oil fatty acid, tall oil fatty acid, rapeseed oil fatty acid, and the like, and oleic acid, linoleic acid, linolenic acid, erucic acid, and the like, which are refined from these, to the Diels-Alder reaction is preferably used. The cyclic structure may be one or two, and in the case of two, the two rings may be independent or continuous. Examples of the cyclic structure include a saturated alicyclic structure, an unsaturated alicyclic structure, and an aromatic ring. Although the carboxyl group can be directly bonded to the cyclic structure, it is preferable that the carboxyl group is bonded to the cyclic structure via an aliphatic chain from the viewpoint of improving solubility and flexibility. The number of carbon atoms between the carboxyl group and the cyclic structure is preferably 2 to 25. In addition, from the viewpoints of improving solubility, improving flexibility, and decreasing the dielectric constant and dielectric tangent, the polybasic acid compound containing a C20 to 60 hydrocarbon group preferably has a chain-like alkyl group with high freedom and hydrophobicity as a portion other than the cyclic structure. It is preferable that there are two or more alkyl groups per cyclic structure. The number of carbon atoms in the alkyl group is preferably 2 to 25.

[0079] Polybasic acid compounds containing C20-60 hydrocarbon groups are generally obtained as a composition of monomers containing a dimer derived from dimer acid (dimerized fatty acid) as a residue, and also containing fatty acid of raw material and fatty acid of trimerization or higher. In particular, it is preferable that the content of monomers containing a dimer derived from dimer acid (dimerized fatty acid) as a residue in 100% by mass of monomers containing C20-60 hydrocarbon groups is 70% by mass or more, preferably 95% by mass or more. In addition, dimers whose degree of unsaturation is reduced by hydrogenation (hydrogenation reaction) are particularly preferably used from the viewpoint of oxidation resistance (particularly coloring in high temperature ranges) and gelation suppression during synthesis. As polybasic acid compounds having C20-60 hydrocarbon groups, it is preferable to use monomers (polybasic acid compounds) containing a dimer derived from monobasic unsaturated fatty acid having 10 to 24 carbon atoms as a residue. Furthermore, it is preferable to use a monomer containing a trimer, which is a tricarboxylic acid, as a residue derived from a monobasic unsaturated fatty acid having 10 to 24 carbon atoms as part of a polybasic acid compound having a C20 to 60 hydrocarbon group.

[0080] The polybasic acid compound having a C20-60 hydrocarbon group can be obtained by a known reaction, but a commercially available product can also be used. Examples of commercially available products include "Pripol 1004", "Pripol 1006", "Pripol 1009", "Pripol 1013", "Pripol 1015", "Pripol 1017", "Pripol 1022", "Pripol 1025", and "Pripol 1040" manufactured by Croda Japan Co., Ltd., and "Empol 1008", "Empol 1012", "Empol 1016", "Empol 1026", "Empol 1028", "Empol 1043", "Empol 1061", and "Empol 1062" manufactured by BASF Japan Co., Ltd. These polybasic acid compounds can be used alone or in combination. Among them, "Pripol 1009" having 36 carbon atoms can be preferably used because it can obtain a polyamide having excellent heat resistance, moist heat resistance, and dielectric constant while maintaining adhesiveness. Pripol 1004 has a structure with 44 carbon atoms, and is therefore suitable for use in that it can provide polyamide with excellent dielectric constant and flexibility. Pripol 1040, which contains approximately 75% by mass of a tricarboxylic acid component, is suitable for use in that it can improve the cohesive strength of polyamide and can be used to improve heat resistance. The cohesive strength can also be improved by using a trifunctional or higher monomer, which will be exemplified as one of the "other polybasic acid compounds" described below, as the trifunctional polybasic acid compound. However, the trifunctional or higher monomer described below has a relatively low molecular weight, whereas the tricarboxylic acid component, which is a trimer, has a relatively large molecular weight, and is therefore more preferable in that the concentration of amide bonds can be efficiently reduced and the dielectric constant and dielectric loss tangent can be reduced.

[0081] [Other polybasic acid compounds] The polybasic acid compounds other than the polybasic acid compounds having a phenolic hydroxyl group and the polybasic acid compounds having a C20-60 hydrocarbon group are not particularly limited within the scope of the present embodiment, and examples thereof include dibasic acid compounds and polybasic acid compounds having three or more functionalities. Examples of dibasic acid compounds include aromatic dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, benzophenone-4,4'-dicarboxylic acid, and 4,4'-biphenyldicarboxylic acid; aliphatic dibasic acids such as oxalic acid, malonic acid, methylmalonic acid, succinic acid, glutaric acid, adipic acid, maleic acid, fumaric acid, malic acid, tartaric acid, thiomalic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, hexadecanedioic acid, and diglycolic acid; and alicyclic dibasic acids such as 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and 1,3-cyclopentanedicarboxylic acid. Examples of polybasic acid compounds having three or more functional groups include trimellitic acid, hydrogenated trimellitic acid, pyromellitic acid, hydrogenated pyromellitic acid, and 1,4,5,8-naphthalenetetracarboxylic acid.

[0082] These polybasic acid compounds may be used alone or in combination with the polybasic acid compounds having a phenolic hydroxyl group or the polybasic acid compounds having a C20-60 hydrocarbon group. Among them, isophthalic acid and 1,4-cyclohexanedicarboxylic acid are preferably used because they can obtain a tough polyamide having better heat resistance while maintaining flexibility. In addition, by using a compound having three or more functional groups, a branched structure can be introduced into the polyamide, which can increase the molecular weight and increase the cohesive strength of the obtained polyamide. As a result, it is possible to improve the dimensional stability and heat resistance in particular without adversely affecting the adhesiveness, flexibility, and electrical insulation properties.

[0083] Furthermore, monofunctional basic compounds can be used in combination with polybasic acid compounds. By using monofunctional compounds, it is possible to reduce the number of carboxyl groups and amino groups that can become terminal functional groups of polyamide, and to control the molecular weight of the resulting polyamide. As a result, it is possible to improve the stability over time of polyamide resins in particular. Examples of monobasic acid compounds include benzoic acid, 4-hydroxybenzoic acid, and 2-ethylhexanoic acid.

[0084] <Polyamine monomer (m2)> The polyamine compound having a phenolic hydroxyl group is not particularly limited, but examples thereof include polyamines represented by the following general formula (2).

[0085] [ka]

[0086] In the formula, R3 represents a direct bond or a group consisting of carbon, hydrogen, oxygen, nitrogen, sulfur, or halogen, and examples thereof include a divalent hydrocarbon group having 1 to 30 carbon atoms, a divalent hydrocarbon group having 1 to 30 carbon atoms in which some or all of the hydrogen atoms have been substituted by halogen atoms, -(C=O)-, -SO2-, -O-, -S-, -NH-(C=O)-, -(C=O)-O-, a group represented by the following general formula (3), and a group represented by the following general formula (4). In the formula, r and s each independently represent an integer of 1 to 20, and R4 represents a hydrogen atom or a methyl group.

[0087] [ka]

[0088] [ka]

[0089] The above R3 is preferably a direct bond.

[0090] In addition, when a compound of general formula (2) is used, R2 in general formula (1), i.e., a divalent linking group which is a polyamine compound residue, is the portion obtained by removing two amino groups from the compound of general formula (2).

[0091] [Polyamine compounds containing C20-60 hydrocarbon groups] Examples of polyamine compounds containing C20-60 hydrocarbon groups include compounds in which the carboxyl groups of the polybasic acid compounds having the above-mentioned C20-60 hydrocarbon groups are converted to amino groups. Examples of commercially available products include "Priamine 1071", "Priamine 1073", "Priamine 1074", and "Priamine 1075" manufactured by Croda Japan, and "Versamine 551" manufactured by BASF Japan. These polyamine compounds can be used alone or in combination. Among them, "Priamine 1071" containing about 20 to 25% by mass of a triamine component, which is a trimer, can improve the cohesive force of polyamide, and can be used preferably from the viewpoint of improving heat resistance. In addition, the use of a triamine, which is a trimer, is preferable from the viewpoint of reducing the dielectric constant and dielectric loss tangent. From the viewpoint of the production stability of the polyamide, the total amount of the triamine trimer and the tricarboxylic acid trimer is preferably 0.1 to 20 mass%, and more preferably 1 to 10 mass%, of 100 mass% of all monomers used to form the polyamide.

[0092] [Other polyamine compounds] Next, polyamine compounds other than the polyamine compound having a phenolic hydroxyl group and the polyamine compound having a C20-60 hydrocarbon group are not particularly limited within the scope of the present embodiment, and examples thereof include diamine compounds and triamine compounds. Examples of diamine compounds include 1,4-diaminobenzene, 1,3-diaminobenzene, 1,2-diaminobenzene, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, 2,3-diaminonaphthalene, 2,6-diaminotoluene, 2,4-diaminotoluene, 3,4-diaminotoluene, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylether, 4,4'-diaminodiphenylether, 4,4'-diamino-1,2-diphenylethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenyl aromatic diamines such as arylsulfone, 3,3'-diaminobenzophenone, and 3,3'-diaminodiphenylsulfone; aliphatic polyamines such as ethylenediamine, 1,3-propanediamine, 1,4-butanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,9-nonanediamine, 1,12-dodecamethylenediamine, and metaxylenediamine; alicyclic diamines such as isophoronediamine, norbornanediamine, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, and piperazine. Examples of polyamine compounds with three or more functional groups include 1,2,4-triaminobenzene and 3,4,4'-triaminodiphenyl ether. In addition, if an aromatic ring is present but the amino group is not directly attached, it is classified as an aliphatic compound.

[0093] These polyamine compounds may be used alone or in combination with the polyamine having a phenolic hydroxyl group or the polyamine having a C20-60 hydrocarbon group. Among them, isophorone diamine and norbornane diamine are preferably used because they can give a tough polyamide having better heat resistance while maintaining flexibility.

[0094] In addition, by using a trifunctional or higher functional group, a branched structure can be introduced into the polyamide, which can increase the molecular weight and the cohesive strength of the resulting polyamide. As a result, the dimensional stability and heat resistance in particular can be improved without adversely affecting the adhesiveness, flexibility, and electrical insulation properties.

[0095] Furthermore, monofunctional amine compounds can be used in combination with polyamine compounds. By using monofunctional compounds, it is possible to reduce the number of carboxyl groups and amino groups that can be terminal functional groups of polyamides, and the molecular weight of the resulting polyamide can be controlled. As a result, it is possible to improve the stability over time of polyamide resins in particular. On the other hand, if the number of carboxyl groups and amino groups that can be terminal functional groups is not reduced by monofunctional compounds, phenol groups and carboxyl groups and / or amino groups will be mixed in the resin, and when a trifunctional or higher compound (C2) that can react with phenolic hydroxyl groups is used in combination, it is desirable to utilize the difference in reactivity between the two to improve processability and adhesion. Examples of monofunctional amine compounds include aniline, 4-aminophenol, and 2-ethylhexylamine.

[0096] The polyamide (A-1) can be obtained by appropriately selecting the polybasic acid monomer (m1) and the polyamine monomer (m2) according to the performance to be particularly improved, such as dimensional stability, adhesion, heat resistance, flexibility, electrical insulation, etc.

[0097] The polyamide (A-1) obtained by polymerization may be a random polymer of a component having a phenolic hydroxyl group and a component having a C20-60 hydrocarbon group, or may be a block polymer. That is, a mixture of multiple polybasic acid monomer compounds may be polymerized with one polyamine compound, a mixture of multiple polybasic acid compounds may be polymerized with a mixture of multiple polyamine compounds, a mixture of one polybasic acid compound may be polymerized with a mixture of multiple polyamine compounds, or a mixture of one polybasic acid compound may be polymerized with multiple polyamine compounds, or a polybasic acid compound may be polymerized with one polyamine compound and another polybasic acid compound or another polyamine compound may be polymerized according to the functional groups remaining at the terminals after polymerizing one polybasic acid compound with one polyamine compound.

[0098] The polyamide (A-1) preferably contains 10 to 95 mol %, more preferably 14 to 92 mol %, and even more preferably 18 to 88 mol %, of a compound containing a C20 to 60 hydrocarbon group out of a total of 100 mol of all monomers used, i.e., the polybasic acid monomer (m1), the polyamine monomer (m2), and the monobasic acid or monofunctional amine compound used as necessary.

[0099] The method for calculating the number of moles of a monomer containing a C20-60 hydrocarbon group will be described below. First, the molecular weight (M) of the monomer containing a C20-60 hydrocarbon group is calculated by the following formula. M = (56.11 × F × 1000) / E F: Number of functional groups of monomers containing C20-60 hydrocarbon groups E: Acid value of monomers containing C20-60 hydrocarbon groups (mgKOH / g) Next, the mass of the compound containing a C20-60 hydrocarbon group subjected to polymerization is divided by the molecular weight (M) to determine the number of moles of the compound containing a C20-60 hydrocarbon group subjected to polymerization. Similarly, the number of moles of each monomer used in the polymerization is calculated, and these are added together to calculate the number of moles of all monomers used in the polymerization. The proportion (mol%) of the compound containing a C20-60 hydrocarbon group can then be calculated by dividing the number of moles of the compound containing a C20-60 hydrocarbon group by the number of moles of all monomers.

[0100] <Polyamide (A-3)> The polyamide (A-3) is a polyamide obtained by mixing the polyamides (a-1) and (a-2). The polyamide (a-1) is obtained by polymerizing the polybasic acid monomer (m3) and the polyamine monomer (m4), and has a phenolic hydroxyl group in the side group and does not have a C20-60 hydrocarbon group. As long as the above conditions are satisfied, other polybasic acid monomers and polyamine monomers can be used appropriately. That is, the polybasic acid monomer (m3) is selected from at least one selected from the group consisting of polybasic acid compounds having a phenolic hydroxyl group and other polybasic acid compounds (excluding polybasic acid compounds having a C20-60 hydrocarbon group), and the polyamine monomer (m4) is selected from at least one selected from the group consisting of polyamine compounds having a phenolic hydroxyl group and other polyamine compounds (excluding polyamine compounds having a C20-60 hydrocarbon group), so that the phenolic hydroxyl group is contained in the polymer. At least one of the polybasic acid monomer (m3) and the polyamine monomer (m4) has a phenolic hydroxyl group. A divalent monomer and a trivalent or higher monomer may be combined to introduce a branched structure and adjust the molecular weight appropriately. It is also possible to use a monovalent monomer to keep the molecular weight appropriate. That is, the polyamide (a-1) is a polyamide having a phenolic hydroxyl group in a side group but not having a C20-60 hydrocarbon group.

[0101] On the other hand, the polybasic acid monomer (m5) is at least one selected from the group consisting of polybasic acid compounds containing a C20-60 hydrocarbon group and other polybasic acid compounds (excluding polybasic acid compounds having a phenolic hydroxyl group), and the polyamine monomer (m6) is at least one selected from the group consisting of polyamine compounds containing a C20-60 hydrocarbon group and other polyamine compounds (excluding polyamine compounds having a phenolic hydroxyl group), and at least one of the polybasic acid monomer (m5) and the polyamine monomer (m6) contains a C20-60 hydrocarbon group. In other words, the polyamide (a-2) is a polyamide having a C20-60 hydrocarbon group but no phenolic hydroxyl group in the side group.

[0102] That is, polyamide (A-3) is a mixture of polyamide (a-1) having a phenolic hydroxyl group in the side group but not having a C20-60 hydrocarbon group, and polyamide (a-2) having a C20-60 hydrocarbon group but not having a phenolic hydroxyl group in the side group. The tri- or higher functional compound (C2) capable of reacting with a phenolic hydroxyl group, which will be described later, is capable of reacting with at least one of a carboxyl group and an amino group in many cases in addition to reacting with a phenolic hydroxyl group. When a thermoplastic resin composition containing polyamide (A-3) and a trifunctional or higher compound (C2) capable of reacting with a phenolic hydroxyl group is heat-cured, if the trifunctional or higher compound (C2) capable of reacting with a phenolic hydroxyl group is one capable of reacting with at least one of a carboxyl group and an amino group, the terminal carboxyl group and the terminal amino group of the polyamide (a-1) containing a phenolic hydroxyl group and the polyamide (a-2) having a C20-60 hydrocarbon group in the polyamide (A-3) can also be utilized in the heat-curing reaction.

[0103] The mixing ratio of the polyamide (a-1) containing a phenolic hydroxyl group to the polyamide (a-2) having a C20-60 hydrocarbon group can be appropriately adjusted depending on the phenolic hydroxyl value and molecular weight of (a-1). The ratio of the polyamide containing a phenolic hydroxyl group to the polyamide having a C20-60 hydrocarbon group is preferably 5:95 to 80:20 (mass ratio), and more preferably 10:90 to 50:50.

[0104] The terms "mixture" and "mixing" in relation to polyamide (A-3) include the following cases: a mixture is obtained in advance from the polyamide (a-1) and the polyamide (a-2), and then a trifunctional or higher compound (C2) capable of reacting with a phenolic hydroxyl group, which will be described later, is blended; a mixture is obtained from the polyamide (a-1), the polyamide (a-2), and a trifunctional or higher compound (C2) capable of reacting with a phenolic hydroxyl group, which will be described later, is blended; a mixture is obtained from the polyamide (a-1) and the trifunctional or higher compound (C2) capable of reacting with a phenolic hydroxyl group, which will be described later, is blended; and a mixture is then blended with the polyamide (a-2), and vice versa.

[0105] The polybasic acid monomer (m3) may be any of the polybasic acid monomers (m1) other than the polybasic acid compounds containing a C20-60 hydrocarbon group. Monobasic compounds may also be used in combination. The polyamine monomer (m4) may be any of the polyamine monomers (m2) other than the polyamine compounds containing a C20-60 hydrocarbon group. Monofunctional amine compounds may also be used in combination.

[0106] The polybasic acid monomer (m5) may be any of the polybasic acid monomers (m1) other than the polybasic acid compounds having a phenolic hydroxyl group. A monobasic compound may also be used in combination. The polyamine monomer (m6) may be any of the polyamine monomers (m2) other than the polyamine compounds having a phenolic hydroxyl group. A monofunctional amine compound may also be used in combination.

[0107] The polyamide (A-3) preferably contains 10 to 95 mol %, more preferably 14 to 92 mol %, and even more preferably 18 to 88 mol %, of a compound containing a C20 to 60 hydrocarbon group out of a total of 100 mol of all monomers used in the formation of the polyamide (A-3), i.e., the polybasic acid monomer (m3), the polyamine monomer (m4), the polybasic acid monomer (m5), the polyamine monomer (m6), and a monobasic acid or a monofunctional amine compound used as needed.

[0108] <Specifications of Polyamide Resin (P2)> Next, the specifications (phenolic hydroxyl value, weight average molecular weight, glass transition temperature) of the polyamide resin (P2) will be described.

[0109] The polyamide resin (P2) may have a terminal carboxyl group or an amino group, or may not have a functional group, so long as the polyamide side group contains a phenolic hydroxyl group. The amount of phenolic hydroxyl groups contained in the polyamide side group can be appropriately adjusted by the type and amount of the trifunctional or higher compound (C2) capable of reacting with the phenolic hydroxyl group.

[0110] [Phenol hydroxyl value] Specifically, the phenolic hydroxyl value of the polyamide resin (P2) is preferably 1 to 80 mgKOH / g, more preferably 5 to 60 mgKOH / g, and even more preferably 5 to 30 mgKOH / g. By using a polyamide having a phenolic hydroxyl value of 1 mgKOH / g or more, a dense crosslinked structure can be formed, and the resistance of the coating film after curing of the thermosetting resin composition can be improved. In addition, by using a polyamide having a phenolic hydroxyl value of 80 mgKOH / g or less, a cured coating film having good hardness, adhesion, and flexibility of the cured product of the thermosetting resin composition can be obtained. In addition, when a polyamide having a phenolic hydroxyl value in the range of 1 to 80 mgKOH / g close to 1 mgKOH / g is used, the adhesion and flexibility of the resulting coating film are improved, while when a polyamide having a phenolic hydroxyl value in the range of 80 mgKOH / g is used, the number of crosslinking points increases, and thus the heat resistance of the finally obtained coating film is improved. In this way, the phenolic hydroxyl value of the polyamide resin (P2) can be adjusted within the range of 1 to 80 mgKOH / g depending on the purpose.

[0111] In the case of (i), the phenolic hydroxyl value can be adjusted by the charge ratio (polymerization composition) of the monomer having a phenolic hydroxyl group among the monomers. In the case of (ii), the phenolic hydroxyl value can be adjusted by the ratio of the monomer having a phenolic hydroxyl group among all the monomers of the polyamides (a-1) and (a-2). For example, by using only 5-hydroxyisophthalic acid having a phenolic hydroxyl group as the polybasic acid compound and only dimer diamine having no phenolic hydroxyl group as the polyamine compound, the phenolic hydroxyl value of the finally obtained polyamide resin (P2) can be close to 80 mgKOH / g, and the heat resistance of the cured coating film can be further improved.

[0112] In addition, in the case of polyamide (A-3) among the polyamide resins (P2), the phenolic hydroxyl value of the mixture is regarded as the phenolic hydroxyl value of the polyamide resin (P2).

[0113] [Weight average molecular weight] Among the polyamide resins (P2), the weight average molecular weight of the polyamide (A-1) is preferably 3,000 to 1,000,000, more preferably 5,000 to 550,000, and even more preferably 10,000 to 300,000, from the viewpoint of handling and adhesiveness and heat resistance when made into a thermosetting resin composition. Among the polyamide resins (P2), the weight average molecular weight of the polyamide (a-1) is preferably 500 to 30,000, more preferably 1000 to 20,000, and even more preferably 1,000 to 10,000, from the viewpoint of solubility in a general-purpose solvent described later. In addition, among the polyamide resins (P2), the weight average molecular weight of the polyamide (a-2) is preferably in the same range as that of the polyamide (A-1).

[0114] [Glass transition temperature of polyamide resin (P2)] The glass transition temperature of the polyamide resin (P2) is preferably −40° C. to 120° C., and more preferably −30° C. to 80° C. By adjusting the glass transition temperature of the polyamide resin (P2) to the range of −40° C. to 120° C., it is possible to suppress extrusion during hot pressing, and further to achieve good embedding properties in the substrate, thereby further improving the adhesiveness.

[0115] The glass transition temperature can be adjusted by appropriately setting the ratio of the polybasic acid compound having a C20-60 hydrocarbon group or the polyamine compound having a C20-60 hydrocarbon group. For example, by increasing the blending ratio of the polybasic acid compound having a C20-60 hydrocarbon group or the polyamine compound having a C20-60 hydrocarbon group, the concentration of amide bonds with high water absorption can be reduced and the flexibility and bending characteristic of dimerized fatty acid can be imparted, so that the glass transition temperature can be adjusted to a range close to -40°C.

[0116] In addition, in the case of polyamide (A-3) among the polyamide resins (P2), the glass transition temperature of the mixture is regarded as the glass transition temperature of the polyamide resin (P2).

[0117] [Solubilities of polyamide resin (P2) in organic solvents] The polyamide resin (P2) is soluble in a wide range of general-purpose organic solvents. The term "soluble" means that the polyamide resin dissolves at 5 parts by mass or more in 95 parts by mass of a mixed solvent of general-purpose solvents such as hydrocarbon solvents, alcohol solvents, ketone solvents, and ester solvents at 25°C. In particular, it is preferable that the polyamide resin dissolves at 5 parts by mass or more in 95 parts by mass of a mixed solvent of toluene / isopropanol = 50 / 50 (mass ratio) at 25°C. Examples of the hydrocarbon solvent include benzene, toluene, ethylbenzene, xylene, cyclohexane, hexane, etc. Examples of the alcohol solvent include methanol, ethanol, propanol, isopropanol, butanol, isobutanol, sec-butanol, tert-butanol, etc. Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc. Examples of the ester solvent include methyl acetate, ethyl acetate, propyl acetate, butyl acetate, etc.

[0118] <Synthesis of polyamide resin (P2)> Next, a method for synthesizing the polyamide resin (P2) will be described. The polymerization conditions for the polyamide resin (P2) are not particularly limited, and known conditions such as melt polymerization, interfacial polymerization, solution polymerization, bulk polymerization, solid-phase polymerization, and combinations of these methods can be used. Generally, industrially, the reaction is carried out at 150 to 300°C for about 1 to 24 hours in the presence or absence of a catalyst. In order to promote the dehydration or dealcoholization reaction and to avoid coloration and decomposition reactions due to high temperatures, it is preferable to carry out the reaction at 180 to 270°C under reduced pressure below atmospheric pressure.

[0119] When synthesizing polyamide (A-1) containing a phenolic hydroxyl group, for example, a flask filled with nitrogen is charged with a polybasic acid compound having a phenolic hydroxyl group or / and a polyamine compound having a phenolic hydroxyl group, a polybasic acid compound having a C20-60 hydrocarbon group or / and a polyamine compound having a C20-60 hydrocarbon group, and ion-exchanged water in a predetermined amount, and the mixture is heated and stirred at 20 to 100°C to dissolve or disperse uniformly. Thereafter, the temperature is gradually increased to 230°C while removing the ion-exchanged water and water generated by the reaction, and when the temperature reaches 230°C, the pressure is reduced to about 15 mmHg and maintained for about 1 hour to obtain polyamide (A-1). When a polybasic acid compound and a polyamine compound are mixed, a salt is formed and the mixture is likely to solidify. When the two are mixed in the presence of ion-exchanged water, the salt formed dissolves or disperses in the ion-exchanged water, so it is preferable to use ion-exchanged water from the viewpoint of safety, etc.

[0120] Specific examples of catalysts that can be used in obtaining the polyamide (A-1) include inorganic phosphorus compounds such as phosphoric acid, phosphorous acid, hypophosphorous acid, pyrophosphoric acid, polyphosphoric acid, and alkali metal salts and alkaline earth metal salts thereof; phosphites such as triphenyl phosphite and diphenyl phosphite; titanium-based catalysts such as tetrabutyl orthotitanate and tetraisopropyl orthotitanate; tin-based catalysts such as dibutyltin oxide, dibutyltin laurate and monobutylhydroxytin oxide; and zirconium-based catalysts such as tetrabutoxyzirconium, zirconium acetate and zirconium octylate.

[0121] These catalysts may be used in combination of two or more kinds. The present invention may be carried out without any problem even if these catalysts are contained in the polyamide resin (P2).

[0122] The by-products are inorganic salt catalysts such as decomposition products of the catalyst used, oxides of the decomposition products or modified products thereof, and by-products such as amide compounds such as oligomers, and these may be contained in the polyamide resin (P2).

[0123] <Trifunctional or higher compound capable of reacting with phenolic hydroxyl group (C2)> The thermosetting resin composition of this embodiment contains the polyamide resin (P2) and a trifunctional or higher compound (C2) capable of reacting with a phenolic hydroxyl group. The trifunctional or higher compound (C2) capable of reacting with a phenolic hydroxyl group will be described. The binder component (II) uses the compound (C2) as a curing agent for the polyamide resin (P2) described above. In addition to the trifunctional or higher compound (C2), a bifunctional compound (C) capable of reacting with a phenolic hydroxyl group [hereinafter also referred to as "compound (C)"] can also be added within the scope of this embodiment. When compound (C) is added, it is preferably 100 parts by mass or less, more preferably 60 parts by mass or less, from the viewpoint of effectively increasing the crosslink density, relative to 100 parts by mass of compound (C2).

[0124] [Epoxy group-containing compound] The trifunctional or higher epoxy group-containing compound that can be used as compound (C2) is not particularly limited as long as it has an epoxy group in the molecule, and can be an epoxy resin such as a glycidyl ether type epoxy resin, a glycidyl amine type epoxy resin, a glycidyl ester type epoxy resin, or a cyclic aliphatic (alicyclic) epoxy resin. From the viewpoint of compatibility with the polyamide resin (P2), an epoxy compound having a viscosity of 10 to 1,000,000 mPa·S at 25°C is preferred.

[0125] Examples of glycidyl ether type epoxy resins include cresol novolac type epoxy resins, phenol novolac type epoxy resins, and tetrakis(glycidyloxyphenyl)ethane. Examples of glycidylamine type epoxy resins include tetraglycidyldiaminodiphenylmethane and tetraglycidylmetaxylylenediamine. As the epoxy group-containing compound, it is preferable to use tetrakis(glycidyloxyphenyl)ethane or tetraglycidyldiaminodiphenylmethane in terms of high adhesion and heat resistance.

[0126] As the epoxy group-containing compound usable as the compound (C), the glycidyl ether type epoxy resin may be, for example, a bisphenol A type epoxy resin, a bisphenol F type epoxy resin, a dicyclopentadiene type epoxy resin, etc. The glycidyl ester type epoxy resin may be, for example, diglycidyl phthalate, diglycidyl hexahydrophthalate, diglycidyl tetrahydrophthalate, etc. Examples of cyclic aliphatic (alicyclic) epoxy resins include 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexane carboxylate, etc. As the epoxy group-containing compound, compound (C2) can be used alone or in combination of two or more kinds, or compound (C2) can be used in combination with compound (C).

[0127] [Isocyanate compounds] The isocyanate group-containing compound that can be used as the compound (C2) is not particularly limited as long as it has three or more isocyanate groups in the molecule. The isocyanate group may be either blocked with a blocking agent or not, but is preferably blocked with a blocking agent.

[0128] The isocyanate group-containing compound that can be used as the bifunctional compound (C) capable of reacting with a phenolic hydroxyl group is not particularly limited, and examples thereof include aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, and 2,6-tolylene diisocyanate, aliphatic diisocyanates such as hexamethylene diisocyanate, and alicyclic diisocyanates such as isophorone diisocyanate, and the like.

[0129] The isocyanate group-containing compound that can be used as the trifunctional or higher compound (C2) that can react with a phenolic hydroxyl group is not particularly limited, and examples thereof include the above-described trimethylolpropane adduct of diisocyanate, a biuret product reacted with water, and a trimer having an isocyanurate ring.

[0130] The blocked isocyanate compound is not particularly limited as long as it is a blocked isocyanate group-containing compound in which the isocyanate group in the isocyanate group-containing compound is protected with ε-caprolactam, MEK oxime, etc. Specific examples include compounds in which the isocyanate group of the isocyanate group-containing compound is blocked with ε-caprolactam, MEK oxime, cyclohexanone oxime, pyrazole, phenol, etc. In particular, hexamethylene diisocyanate trimer having an isocyanurate ring and blocked with MEK oxime or pyrazole is very preferable when used in this embodiment because it is excellent in storage stability, as well as adhesive strength to bonding materials such as polyimide and copper, and solder heat resistance.

[0131] [Carbodiimide group-containing compounds] Examples of carbodiimide group-containing compounds that can be used as the trifunctional or higher compound (C2) that can react with a phenolic hydroxyl group include the Carbodilite series manufactured by Nisshinbo Industries, Inc. Among these, Carbodilite V-01, 03, 05, 07, and 09 are preferred because they have excellent compatibility with organic solvents.

[0132] [Metal chelate compounds] Metal chelate compounds usable as the trifunctional or higher compound (C2) capable of reacting with a phenolic hydroxyl group include aluminum chelate compounds, titanium chelate compounds, and zirconium chelate compounds, but are not particularly limited because chelate bonds can be formed with various metals such as iron, cobalt, indium, etc. as the central metal. The number of functional groups of the metal chelates and metal alkoxides and metal acylates described below is calculated as the valence of the central metal, and trifunctional or higher compounds, i.e., compounds with a central metal valence of 3 or higher, can be used as the compound (C2).

[0133] Representative examples of the aluminum chelate compound used in the binder component (II) include aluminum acetylacetonate and aluminum ethylacetoacetate.

[0134] Representative examples of titanium chelate compounds include titanium acetylacetonate, titanium ethyl acetoacetate, titanium octylene glycolate, titanium lactate, titanium triethanolamine, polytitanium acetylacetonate, etc. Representative examples of zirconium chelate compounds include zirconium acetylacetonate, zirconium ethyl acetylacetonate, zirconium lactate ammonium salt, etc.

[0135] [Metal alkoxide] Examples of metal alkoxide compounds include aluminum alkoxide compounds, titanium alkoxide compounds, and zirconium alkoxide compounds, but are not particularly limited because alkoxide bonds can be formed with various metals such as iron, cobalt, and indium as the central metal.

[0136] Representative examples of the aluminum alkoxide compound include aluminum isopropylate, aluminum butyrate, and aluminum ethylate. Representative examples of the titanium alkoxide compound include isopropyl titanate, normal butyl titanate, butyl titanate dimer, tetraoctyl titanate, tertiary amyl titanate, tertiary butyl titanate, and tetrastearyl titanate. Representative examples of the zirconium alkoxide compound include normal propyl zirconate and normal butyl zirconate.

[0137] [Metal Acylates] Examples of metal acylate compounds include aluminum acylate compounds, titanium acylate compounds, and zirconium acylate compounds, but are not particularly limited because alkoxide bonds can be formed with various metals such as iron, cobalt, and indium as the central metal.

[0138] The trifunctional or higher functional compound (C2) includes a functional group containing three or more functional groups of the same type in one molecule, as well as a functional group containing three or more functional groups in total. For example, a compound containing a mixture of a chelate, an alkoxide, and an acylate in one molecule can be suitably used.

[0139] The compound (C2) may be used alone or in combination with a plurality of compounds. In the case of using a plurality of compounds in combination, a synergistic effect is exhibited, such as improved processability and adhesiveness, utilizing the difference in reactivity between the compounds when using a polyamide resin (P2) having a mixture of phenol groups and carboxyl groups and / or amino groups, and this is desirable. Among these, "at least one selected from the group consisting of metal chelates, metal alkoxides, and metal acylates" and "a trifunctional or higher epoxy group-containing compound" are preferred because they have significantly different reactivities and can be expected to have a large synergistic effect due to the different characteristics of the physical properties that can be improved. The amount of the compound (C2) used may be determined in consideration of the application of the curable resin composition, and is not particularly limited, but is preferably added in a ratio of 0.5 to 100 parts by mass, more preferably 1 to 80 parts by mass, relative to 100 parts by mass of the polyamide resin (P2). By using the compound (C2), the crosslink density of the curable resin composition can be adjusted to an appropriate value, and various physical properties of the coating film after curing can be further improved. When the amount of compound (C2) used is close to 0.5 parts by mass, the crosslink density of the coating film after heat curing can be prevented from becoming too high, and the desired flexibility and adhesiveness can be exhibited. Furthermore, the increase in polar functional groups can be suppressed, and the desired dielectric constant, dielectric loss tangent, and moist heat resistance can be exhibited. Furthermore, when the amount used is close to 100 parts by mass, the crosslink density after heat curing can be further increased, and as a result, the coating film resistance, such as the electrical insulation property of the coating film, can be improved.

[0140] In the binder component (II), a compound capable of reacting with a carboxyl group or a compound capable of reacting with an amino group can be used in combination with the compound (C2). Examples of the compound capable of reacting with a carboxyl group include aziridine compounds, β-hydroxyalkylamide group-containing compounds, and dicyandiamide. Examples of the compound capable of reacting with an amino group include maleimide compounds.

[0141] In particular, 2,2'-bishydroxymethylbutanol tris[3-(1-aziridinyl)propionate] is preferably used in this embodiment because, when used in this embodiment, it can suppress extrusion during hot pressing and improve the heat resistance while maintaining the flexibility of the cured coating film.

[0142] The binder component (II) may contain a compound that directly contributes to the curing reaction as a curing accelerator, such as a phosphine compound, a phosphonium salt, an imidazole compound, or a tertiary amine compound.

[0143] The binder component (II) essentially contains the polyamide resin (P2) and the compound (C2), and may contain an organic solvent as appropriate. Examples of low-boiling point solvents include toluene, cyclohexane, hexane, isopropanol, methyl ethyl ketone, and ethyl acetate. Examples of high-boiling point solvents include carbitol acetate, methoxypropyl acetate, cyclohexanone, diisobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and dimethyl sulfoxide. The organic solvents may be used alone or in combination as appropriate. When a solvent is used in producing the polyamide resin (P2), the binder component (II) may contain the solvent, or the solvent used in producing the polyamide resin (P2) may be removed by distillation, and another solvent may be added to obtain a liquid binder component (II). The solid content of the binder component (II) is, for example, 5 to 80% by mass.

[0144] <Other additives> The binder component (II) may further contain other components (additives) exemplified in the binder component (I) as optional components within a range that does not impair the purpose. Dyes, pigments, flame retardants, antioxidants, polymerization inhibitors, defoamers, leveling agents, ion collectors, moisturizers, viscosity modifiers, preservatives, antibacterial agents, antistatic agents, antiblocking agents, ultraviolet absorbers, infrared absorbers, fillers, etc. may be added. As a filler for imparting a flame retardant, etc., the same fillers as those in the binder component (I) can be suitably used. In particular, when a cured product of the thermosetting resin composition of this embodiment is used for insulating members (e.g., circuit protection films, coverlay layers, interlayer insulating materials, etc.) that directly contact circuits in electronic material applications, or members (printed wiring boards, support boards, etc.) that may become hot around the circuits, it is preferable to use a flame retardant in combination.

[0145] [[Binder component (III)]] The binder component (III) contains a polyurethane resin (P3) and an epoxy compound (C3) capable of reacting with the polyurethane resin. The polyurethane resin also includes a polyurethane polyurea resin.

[0146] The following are examples of methods for synthesizing the carboxyl group-containing polyurethane resin (P3). For example, it can be produced by reacting a polyol compound, a diisocyanate compound, and a diol compound having a carboxyl group. In addition, when synthesizing the polyurethane resin (P3), an excess of a diisocyanate compound is added to synthesize a carboxyl group-containing urethane prepolymer having an isocyanate group at its terminal, and then a diamine compound is reacted to produce a urethane urea resin into which a urea group has been introduced.

[0147] The polyol compound refers to a compound having a weight average molecular weight of 500 or more and two or more hydroxyl groups. Examples of the polyol compound include polyether polyols such as polyethylene oxide, polypropylene oxide, block copolymers or random copolymers of ethylene oxide / propylene oxide, polytetramethylene glycol, block copolymers or random copolymers of tetramethylene glycol and neopentyl glycol, polyester polyols which are condensates of polyhydric alcohols or polyether polyols with polybasic acids such as maleic anhydride, maleic acid, fumaric acid, itaconic anhydride, itaconic acid, adipic acid, and isophthalic acid, polycarbonate polyols obtained by the reaction of glycol or bisphenol with a carbonate ester, or the reaction of glycol or bisphenol with phosgene in the presence of an alkali, caprolactone-modified polyols such as caprolactone-modified polytetramethylene polyols, polyolefin polyols, polybutadiene polyols such as hydrogenated polybutadiene polyols, and silicone polyols. These polyol compounds may be used alone or in combination of two or more kinds.

[0148] The diol compound having a carboxyl group is not particularly limited as long as it is a compound having two hydroxyl groups and one or more carboxyl groups in the molecule, and examples thereof include dimethylolbutanoic acid, dimethylolpropionic acid, and derivatives thereof (caprolactone adducts, ethylene oxide adducts, propylene oxide adducts, etc.), 3-hydroxysalicylic acid, 4-hydroxysalicylic acid, 5-hydroxysalicylic acid, 2-carboxy-1,4-cyclohexanedimethanol, etc. One type of these diol compounds having a carboxyl group may be used alone, or two or more types may be used in combination.

[0149] Examples of the diisocyanate compound include aromatic diisocyanates, aliphatic diisocyanates, araliphatic diisocyanates, and alicyclic diisocyanates.

[0150] Examples of aromatic diisocyanates include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.

[0151] Examples of the aliphatic diisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0152] Examples of the aromatic aliphatic diisocyanate include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0153] Examples of alicyclic diisocyanates include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate [also known as isophorone diisocyanate], 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,3-bis(isocyanatemethyl)cyclohexane, 1,4-bis(isocyanatemethyl)cyclohexane, etc. These diisocyanate compounds may be used alone or in combination of two or more.

[0154] The diamine compound acts as a chain extender, and examples thereof include diaminobenzene, diaminotoluene, diaminodimethylbenzene, diaminomesitylene, diaminochlorobenzene, diaminonitrobenzene, diaminoazobenzene, diaminonaphthalene, diaminobiphenyl, diaminodimethoxybiphenyl, diaminodiphenyl ether, diaminodimethyldiphenyl ether, methylene dianiline, methylene bis(methylaniline), methylene bis(dimethylaniline), methylene bis(methoxyaniline), methylene bis(dimethoxyaniline), methylene bis(ethylaniline), methylene bis(diethylaniline), methylene bis(ethoxyaniline), methylene bis(diethoxyaniline), methylene bis(dibromoaniline), isopropylidenedianiline, hexafluoroisopropylidenedianiline, diaminobenzophenone, diaminodimethylbenzophenone, diaminoanthraquinone, diaminodiphenyl thioether, diaminodimethyl Aromatic polyamines such as diphenyl thioether, diaminodiphenyl sulfone, diaminodiphenyl sulfoxide, and diaminofluorene; aliphatic polyamines such as ethylene polyamines, propane polyamines, hydroxypropane polyamines, butane polyamines, heptane polyamines, hexane polyamines, diaminodiethylamine, diaminodipropylamine, azapentane polyamines, triazaundecane polyamines, nonamethylene polyamines, undecamethylene polyamines, dodecamethylene polyamines, methyl pentamethylene polyamines, 2,2,4 (or 2,4,4)-trimethylhexamethylene polyamines, and polyamine compounds having 20 to 48 carbon atoms; alicyclic polyamines such as bis-(4,4'-aminocyclohexyl)methane, metaxylylene polyamines, paraxylylene polyamines, isophorone polyamines, norbornane polyamines, cyclopentane polyamines, cyclohexane polyamines, piperazine, and homopiperazine can be used.

[0155] The polyurethane resin (P3) is preferably a urethane urea resin having a urea group introduced therein, which can improve adhesiveness and flexibility.

[0156] <Epoxy compound (C3)> The epoxy compound (C3) having three or more functionalities and containing an epoxy group may be any compound having an epoxy group in the molecule, and is not particularly limited. Specific examples include epoxy resins such as glycidyl ether type epoxy resins, glycidyl amine type epoxy resins, glycidyl ester type epoxy resins, and cyclic aliphatic (alicyclic) epoxy resins. Specific examples include compounds similar to the compound (C2) exemplified in the binder component (II). In addition, epoxy compounds having at least one or more nitrogen atoms in the molecule can be exemplified.

[0157] By using an epoxy compound having at least one tertiary nitrogen atom in the molecule, it is possible to improve the dielectric constant and dielectric tangent while also improving metal adhesion and heat resistance. This is because the high reactivity, which is a unique property of epoxy compounds having tertiary nitrogen atoms, makes it possible to increase the reaction rate under specified curing conditions, improve the crosslink density of the cured product, and obtain a high elastic modulus. As a result, it is possible to suppress the water absorption rate, which determines the dielectric properties. In addition, nitrogen atoms can take various coordination forms, which strongly support the adhesion between metals and organic compounds and also provide excellent metal adhesion.

[0158] When an epoxy compound having at least one or more tertiary nitrogen atoms in the molecule is used, the reaction rate under a predetermined curing condition can be increased by the nitrogen atoms contained in the compound, so that the decrease in elastic modulus and the increase in water absorption rate due to unreacted low molecular weight compounds can be suppressed, and furthermore, the metal adhesion derived from the nitrogen atoms can be increased, so that good dielectric properties and various properties can be simultaneously satisfied. The epoxy compound having at least one or more tertiary nitrogen atoms in the molecule is not particularly limited as long as it has at least one nitrogen compound in a compound containing an epoxy group in the molecule. Specific examples of the epoxy compound having at least one or more tertiary nitrogen atoms in the molecule include N-glycidylphthalimide and epoxy compounds having structures represented by the following formulas (5) to (15).

[0159] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka]

[0160] In the formula, X represents an aliphatic group having 0 to 6 carbon atoms or an aromatic group; Y represents any one of a methylene group, an ethylene group, a trimethylene group, an ethylidene group, an isopropylidene group, a vinylene group, a vinylidene group, an oxy group, an imino group, a thio group, and a sulfonyl group; R1 to R3 represent a hydrogen atom or an aliphatic group having 1 to 6 carbon atoms; and j represents an integer of 0 to 4.

[0161] All of them are preferable because they have excellent dielectric properties from the viewpoint of thermosetting property and low moisture absorption, but 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylylenediamine, triglycidyl-m-aminophenol, triglycidyl-p-aminophenol, and 4,4'-methylenebis[N,N-bis(oxiranylmethyl)aniline] are particularly preferable because they are polyfunctional and tend to improve the heat resistance of the cured product of the thermosetting resin composition in addition to the dielectric properties when used in the binder component (III). Also, N,N-diglycidylaniline and N,N-diglycidyltoluidine are bifunctional and tend to improve the flexibility of the cured coating film and the adhesion to polyimide and copper in addition to the dielectric properties when used in the binder component (III), and are preferable.

[0162] [[Binder component (IV)]] The binder component (IV) contains a polyimide resin (P4) containing a hydrocarbon group having 20 to 60 carbon atoms (hereinafter also referred to as a C20 to 60 hydrocarbon group) and a bifunctional or higher compound (C4) capable of reacting with the polyimide resin (P4). The polyimide resin (P4) is obtained through a process of condensing a polyamine compound and a carboxylic polyanhydride, a process of forming an imide group, and the like. Here, the polyamine compound is a substance having two or more amino groups per monomer, and is a primary amine or a secondary amine. In addition, the carboxylic polyanhydride refers to a compound having two or more carboxylic anhydride groups in the molecule. The polyamine compound is preferably a diamine compound, and the carboxylic polyanhydride is preferably a tetracarboxylic dianhydride.

[0163] The polyimide resin (P4) may contain a C20-60 hydrocarbon group in any of its monomers. A diamine compound is suitable as the monomer having a C20-60 hydrocarbon group in terms of ease of synthesis of the monomer. A diamine compound having a C20-60 hydrocarbon group can be obtained, for example, by converting the carboxyl group of a polybasic acid compound containing a C20-60 hydrocarbon group, explained in the binder component (II) above, to an amino group.

[0164] The diamine compound containing a C20-60 hydrocarbon group can be a compound obtained by converting a carboxyl group of a polybasic acid compound having a cyclic structure of 5 to 10 carbon atoms (see binder component (II)) obtained by reacting a monobasic unsaturated fatty acid having one or more double or triple bonds of 10 to 24 carbon atoms into an amino group. For example, a compound obtained by converting a carboxyl group of a polybasic acid compound containing a dimerized fatty acid (dimer acid) obtained by subjecting natural fatty acids such as soybean oil fatty acid, tall oil fatty acid, rapeseed oil fatty acid, and the like, which are refined from these, to a Diels-Alder reaction, can be exemplified. The ring structure may be one or two, and in the case of two, the two rings may be independent or continuous. In addition, the ring structure may not be present, and a mixture of a ring structure and a compound having no ring structure may be present. By using a diamine compound derived from a dimer acid, a dimer skeleton can be easily introduced into the polyimide resin (P4).

[0165] The cyclic structure may be a saturated alicyclic structure, an unsaturated alicyclic structure, or an aromatic ring. The amino group (amino group converted from a carboxyl group) may be directly bonded to the cyclic structure, but from the viewpoint of improving solubility and flexibility, it is preferable that the amino group is bonded to the cyclic structure via an aliphatic chain. The number of carbon atoms between the amino group and the cyclic structure is preferably 2 to 25. In addition, the polyamine compound containing a C20 to 60 hydrocarbon group preferably has a chain-like alkyl group having high freedom and hydrophobicity as a portion other than the cyclic structure, from the viewpoint of improving solubility, flexibility, and reducing the dielectric constant and dielectric loss tangent. It is preferable that one cyclic structure has two or more alkyl groups. It is preferable that the number of carbon atoms of the alkyl group is 2 to 25.

[0166] The polyamine compound containing a C20-60 hydrocarbon group is preferably obtained by converting the carboxyl group of the composition of the raw material fatty acid or the trimerized or higher fatty acid into an amino group, and the main component (70% by mass or more) is a monomer containing a dimer skeleton derived from a dimer acid (dimerized fatty acid). The content of the so-called dimer skeleton-containing monomer, which has a dimer derived from a dimer acid (dimerized fatty acid) as a residue, in 100% by mass of the monomer containing a C20-60 hydrocarbon group is more preferably 90% by mass or more, and even more preferably 95% by mass or more. In addition, a dimer whose degree of unsaturation is reduced by hydrogenation (hydrogenation reaction) is particularly preferably used from the viewpoint of oxidation resistance (particularly coloring in a high temperature range) and gelation suppression during synthesis. As the polyamine compound having a C20-60 hydrocarbon group, it is preferable to use a monomer (polyamine compound) containing a dimer derived from a monobasic unsaturated fatty acid having 10 to 24 carbon atoms as a residue. Furthermore, it is preferable to use a monomer containing, as a part of the polyamine compound having a C20-60 hydrocarbon group, a residue of a trimer, which is a triamine obtained by converting a tricarboxylic acid derived from a monobasic unsaturated fatty acid having 10 to 24 carbon atoms. By using a polyamine compound having three or more functional groups, a branched structure can be introduced into the polyimide resin (P4), which can have a high molecular weight and increase the cohesive strength of the resulting polyimide resin (P4).

[0167] Commercially available dimer diamines include, for example, Priamine 1071, Priamine 1073, Priamine 1074, Priamine 1075 (all manufactured by Croda Japan Ltd.), Versamine 551 (manufactured by BASF Japan Ltd.), etc. The dimer diamines can be used alone or in combination of two or more kinds.

[0168] The polyamine compound used in the polymerization of the polyimide resin (P4) may be the polyamine compound having a C20-60 hydrocarbon group as described above, but other polyamine compounds may be used within the scope of the present invention. Specific examples include the compounds exemplified in [Other polyamine compounds] described in the binder component (II). The other polyamine compounds are preferably 50 mol % or less, more preferably 25 mol % or less of the total amount of the polyamine compounds used in the polyimide resin (P4).

[0169] The carboxylic acid polyanhydride may be a known monomer. Specifically, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylethertetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride, 4,4'-(Hexafluoroisopropylidene)diphthalic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-cyclohexene-1,2 dicarboxylic anhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, methylene-4,4'-diphthalic dianhydride, 1,1-ethylidene-4,4'-diphthalic dianhydride, 2,2-propylidene-4,4'-diphthalic dianhydride, 1,2-ethylene-4,4'-diphthalic dianhydride, 1,3-trimethyl 1,4-Tetramethylene-4,4'-diphthalic dianhydride, 1,5-Pentamethylene-4,4'-diphthalic dianhydride, 4,4'-oxydiphthalic dianhydride, p-phenylenebis(trimellitate anhydride), thio-4,4'-diphthalic dianhydride, sulfonyl-4,4'-diphthalic dianhydride, 1,3-bis(3,4-dicarboxyphenyl)benzene dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride Anhydride, 1,3-bis[2-(3,4-dicarboxyphenyl)-2-propyl]benzene dianhydride, 1,4-bis[2-(3,4-dicarboxyphenyl)-2-propyl]benzene dianhydride, bis[3-(3,4-dicarboxyphenoxy)phenyl]methane dianhydride, bis[4-(3,4-dicarboxyphenoxy)phenyl]methane dianhydride, 2,2-bis[3-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, bis(3,4-dicarboxyphenoxy)dimethylsilane dianhydride, 1,3-bis(3,4-dicarboxyphenyl)-1,1,3,3-tetramethyldisiloxane dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, cyclobutanetetracarboxylic dianhydride (e.g., 1,2,3,4-cyclobutanetetracarboxylic dianhydride, tetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, cyclohexanetetracarboxylic dianhydride (e.g., 1,2,4,5-cyclohexanetetracarboxylic dianhydride, etc.), 9,9-bis[4-(3,1-, 3,2-, 3,3- or 3,4-dicarboxyphenoxy)phenyl]fluorene dianhydride, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride, and 1,2,7, 8-Phenanthrenetetracarboxylic dianhydride, 1,2,4,5-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,4,5,8-decahydronaphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,5,6-hexahydronaphthalenetetracarboxylic dianhydride, 2,6-dichloro-1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,7-dichloro-1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-tetrachloro-1,4,5,8-naphthalene Tetracarboxylic acid dianhydrides, 1,8,9,10-phenanthrenetetracarboxylic acid dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, benzene-1,2,3,4-tetracarboxylic acid dianhydride, 3,4,3',4'-benzophenonetetracarboxylic dianhydride, etc. Among these, aromatic carboxylic polyanhydrides are preferred from the viewpoint of adhesion and compatibility with amines containing a C20-60 hydrocarbon group, and aromatic tetracarboxylic dianhydrides are more preferred. Among these, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylethertetracarboxylic dianhydride, and 4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride are particularly preferred from the viewpoint of compatibility with polyamine compounds during synthesis and dielectric properties as a resin. The carboxylic polyanhydrides can be used alone or in combination of two or more.

[0170] A more preferred example of the polyimide resin (P4) is a polyimide resin (P4) that contains structural units derived from an aromatic carboxylic polyanhydride and structural units derived from a polyamine compound having a hydrocarbon group having 20 to 60 carbon atoms, and in which 70 mass % or more of the hydrocarbon group having 20 to 60 carbon atoms is a group derived from a dimer skeleton.

[0171] The reactive functional group of the polyimide resin (P4) is not limited, but at least one of an amino group and an anhydride group is preferable. The reactive functional group is present on the side chain or terminal of the polyimide resin (P4). The polyimide resin (P4) having an amine or an anhydride group at the molecular terminal can be easily obtained by adjusting the ratio of the amount of the diamine compound and the tetracarboxylic dianhydride. More preferable is a polyimide resin (P4) having an acid anhydride group at the terminal by blending an excessive amount of an acid dianhydride (blended at 50 mol % or more). In addition, after blending an excessive amount of a diamine compound (blended at 50 mol % or more) to obtain a polyimide resin having a diamine compound at the terminal or a polyimide resin precursor before forming an imide ring, the polyimide resin may be reacted with maleic anhydride to introduce an acid anhydride group at the terminal.

[0172] <Synthesis of polyimide resin (P4)> The polymerization conditions for the polyimide resin (P4) are not particularly limited. For example, it is obtained by polymerizing a polyamine compound and a tetracarboxylic dianhydride in a solvent. Specifically, in the presence or absence of a catalyst, a polyamic acid solution is obtained by heating, for example, at 50 to 150°C in an organic solvent for about 0.1 to 4 hours. Then, for example, a polyimide resin is obtained by dehydrating and cyclizing at 80 to 250°C for 0.5 to 20 hours. A terminal blocking agent may be added to control the polymerization reaction. The terminal blocking agent is not particularly limited, and known agents can be used. When synthesizing the polyimide resin (P4), known additives such as a dehydrating agent and a reaction catalyst can be appropriately used.

[0173] The weight average molecular weight of the polyimide resin (P4) is preferably in the range of 10,000 to 120,000, more preferably 12,000 to 100,000, and even more preferably 15,000 to 70,000, from the viewpoints of handleability and adhesiveness and heat resistance when made into a thermosetting resin composition.

[0174] The acid value of the polyimide resin (P4) is not particularly limited, but is preferably from 0.5 to 100, more preferably from 1 to 60, and even more preferably from 2 to 30. By adjusting the acid value to 0.5 to 100, a resin having superior adhesiveness and heat resistance can be obtained.

[0175] The amine value of the polyimide resin (P4) is not particularly limited, but is preferably 0 to 50, more preferably 0 to 45, and further preferably 0 to 30. By adjusting the amine value to 0 to 50, a resin having an excellent pot life as a thermosetting resin composition can be obtained.

[0176] <Compounds with two or more functional groups (C4)> The bifunctional or higher compound (C4) is a compound having a group capable of reacting with the reactive functional group of the polyimide resin (P4) to construct a crosslinked structure. Suitable examples include an epoxy compound having a bifunctional or higher epoxy group, an isocyanate compound having a bifunctional or higher isocyanate group, a maleimide compound having a bifunctional or higher maleimide group, and a carbodiimide compound having a bifunctional or higher carbodiimide group. Among these, an epoxy compound is preferred from the viewpoint of forming a cured product having excellent heat resistance and adhesiveness, as well as excellent dielectric properties.

[0177] Among the epoxy compounds, from the viewpoint of increasing the crosslink density of the cured product and more effectively increasing the adhesiveness and heat resistance, a trifunctional or higher epoxy compound is preferred. As the trifunctional or higher epoxy compound, an epoxy resin such as a glycidyl ether type epoxy resin, a glycidyl amine type epoxy resin, a glycidyl ester type epoxy resin, or a cyclic aliphatic (alicyclic) epoxy resin can be used. Specific examples include the compounds exemplified in the binder component (II) and the binder component (III). From the viewpoint of improving the dielectric constant and the dielectric loss tangent while improving the metal adhesiveness and heat resistance, an epoxy compound having at least one or more nitrogen atoms in the molecule is preferred, and an epoxy compound having a tertiary nitrogen atom is more preferred.

[0178] The high reactivity, which is a unique property of epoxy compounds with tertiary nitrogen atoms, allows the reaction rate to be increased under specified curing conditions, improving the crosslink density of the cured product and achieving a high elastic modulus. As a result, the water absorption rate, which affects the dielectric properties, can be suppressed. In addition, nitrogen atoms can take various coordination forms, which strongly supports adhesion between metals and organic compounds and also provides excellent metal adhesion.

[0179] When an epoxy compound having at least one or more tertiary nitrogen atoms in the molecule is used, the reaction rate under a predetermined curing condition can be increased by the nitrogen atoms contained in the compound, so that the decrease in elastic modulus and the increase in water absorption rate caused by unreacted low molecular weight compounds can be suppressed. Furthermore, since the metal adhesion derived from the nitrogen atoms can be increased, good dielectric properties and various properties can be simultaneously satisfied. The epoxy compound having at least one or more tertiary nitrogen atoms in the molecule is not particularly limited as long as it has at least one nitrogen compound in a compound containing an epoxy group in the molecule. Examples of the epoxy compound having at least one or more tertiary nitrogen atoms in the molecule include epoxy compounds having structures represented by formulas (5) to (15) exemplified in the binder component (III).

[0180] Examples of the isocyanate compound include the compounds exemplified as compound (C2) in the binder component (II). Examples of the carbodiimide group-containing compound include the compounds exemplified as the binder component (II).

[0181] According to the thermosetting resin composition in which the binder component (IV) is combined with a thermally conductive filler, a highly reliable composition having excellent thermal conductivity and dielectric properties can be provided. Suitable examples of the thermally conductive filler are as described above. Particularly suitable examples include a combination of the binder component (IV) with a boron nitride filler, and a combination of the binder component (IV) with boron nitride / alumina, and it is more suitable to use boron nitride / alumina in a mass ratio of 60 / 40 to 95 / 5. By using the binder component (IV) with boron nitride / alumina in a range of 60 / 40 to 95 / 5, a cured product having a better balance of adhesive strength, dielectric properties, and thermal conductivity can be provided.

[0182] [[Thermosetting resin composition]] In addition to the above-mentioned components, the thermosetting resin composition of the present embodiment may contain an antioxidant to prevent oxidation of the resin. Specific examples of the antioxidant include hindered phenol-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, amine-based antioxidants, and copper-based antioxidants.

[0183] Known compounds can be used as the hindered phenol-based antioxidant. These compounds can be used alone or in combination. Among these hindered phenol-based antioxidants, phenols with two or more functionalities are preferred, and semi-hindered types such as triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate] (IRGANOX245) are preferred in terms of resistance to discoloration.

[0184] The phosphorus-based antioxidant is at least one selected from inorganic and organic phosphorus-based antioxidants. Examples of inorganic phosphorus-based antioxidants include hypophosphites such as sodium hypophosphite, phosphites, etc. As the organic phosphorus-based antioxidant, commercially available phosphite-based organic phosphorus-based antioxidants can be used, but organic phosphorus-containing compounds that do not generate phosphoric acid by thermal decomposition are preferred. As such organic phosphorus-containing compounds, known compounds can be used.

[0185] The thermosetting resin composition of the present embodiment can use a known amine-based antioxidant. Secondary arylamines can also be used as the amine-based antioxidant. Secondary arylamines refer to amine compounds containing two carbon radicals chemically bonded to a nitrogen atom, in which at least one, preferably both, of the carbon radicals are aromatic.

[0186] In the thermosetting resin composition of the present embodiment, a known sulfur-based antioxidant can be used.

[0187] In the thermosetting resin composition of the present embodiment, a copper-based antioxidant containing a mixture of a copper salt and an alkali metal halide and / or an alkaline earth metal halide can be used. For example, a stabilizer containing a mixture of copper(I) iodide and potassium iodide can be used, but is not limited thereto.

[0188] By using a thermosetting resin composition containing any one of the binder components (I) to (IV) and a thermally conductive filler, it is possible to provide a highly reliable thermosetting resin composition having excellent electrical insulation properties, thermal conductivity, and dielectric properties, and a cured product thereof.

[0189] The thermally conductive resin composition is preferably produced by stirring and mixing the binder component and the thermally conductive filler with a solvent. A general stirring method can be used for stirring and mixing, for example, a Scandex, a paint conditioner, a sand mill, a mortar mill, a media-less dispersing machine, a three-roll mill, a bead mill, etc., and these can be combined. The solvent here means a dispersion medium.

[0190] After stirring and mixing, it is preferable to perform a defoaming step in order to remove air bubbles from the thermally conductive resin composition. The defoaming method is not particularly limited and can be performed using a general method, for example, vacuum defoaming, ultrasonic defoaming, etc.

[0191] Various conventional additives can be added to the thermally conductive resin composition as necessary. Examples of the various additives include a coupling agent for improving the adhesion to the substrate, a dispersant for improving the dispersibility of the thermally conductive filler and the binder component, an ion trapping agent for improving the insulation reliability when absorbing moisture, and a leveling agent. These may be used alone or in combination.

[0192] The coating method is not particularly limited, and any known method can be used, such as knife coating, die coating, lip coating, roll coating, curtain coating, bar coating, gravure coating, flexo coating, dip coating, spray coating, spin coating, etc. Alternatively, the composition may be poured into a mold and cast.

[0193] When the thermosetting resin composition is made into a sheet, a substrate may be used as appropriate. For example, the substrate may be a plastic film such as a polyester film, a polyethylene film, a polypropylene film, or a polyimide film, or a film obtained by subjecting the plastic film to a release treatment (hereinafter, referred to as a release film). Furthermore, a metal such as aluminum, copper, stainless steel, or beryllium copper, or a foil of an alloy thereof may be used as the substrate. EXAMPLES

[0194] The present invention will be described in more detail below with reference to examples, but the following examples are not intended to limit the scope of the invention. In the examples, "parts" and "%" represent "parts by mass" and "% by mass", respectively, and Mw represents the weight average molecular weight. In addition, Example 1 in the originally filed specification shall be read as Reference Example 1 for the purpose of conforming to the scope of Claim 1.

[0195] [Synthesis Example 1] <Synthesis example of styrene-based elastomer (P1)> 100g of styrene-based elastomer (P1) with a polymer block ratio of styrene:[ethylene / butylene]=15:85 (mass%) and a weight average molecular weight of 55,000 was dry-blended with 1.03g of maleic anhydride, 0.1g of benzoyl peroxide, and 0.6g of Irganox 1010 (BASF Japan, antioxidant), and further mixed and melt-kneaded using a 32mm twin-screw extruder with a vent to obtain a pellet-shaped sample. The temperatures of the twin-screw extruder during mixing and melt-kneading were 40°C at the bottom of the hopper, 80°C in the mixing zone, 170°C in the reaction zone, and 180°C at the die. 85 parts by mass of acetone and 85 parts by mass of heptane were added to 100 parts by mass of the obtained pellet-like sample, and the mixture was heated and stirred at 85°C for 2 hours in a pressure-resistant reactor. After the operation was completed, the pellets were collected using a wire net and vacuum-dried at 140°C and 0.1 Torr for 20 hours to obtain a styrene-butadiene block copolymer having an acid anhydride group. The molecular weight distribution was narrow, with a weight average molecular weight of 60,000, a total acid value of 11.2 mgCH3ONa / g, and an acid anhydride value of 5.6 mgCH3ONa / g.

[0196] The Mw of Synthesis Example 1 was measured using a GPC (gel permeation chromatography) "HPC-8020" manufactured by Tosoh Corporation. GPC is a liquid chromatography that separates and quantifies substances dissolved in a solvent (THF; tetrahydrofuran) based on the difference in their molecular size. The measurement in the present invention was performed using two "LF-604" columns (Showa Denko KK: GPC column for rapid analysis: 6 mm ID x 150 mm size) connected in series, at a flow rate of 0.6 mL / min and a column temperature of 40°C, and the weight average molecular weight (Mw) was determined in polystyrene equivalent.

[0197] The total acid value of Synthesis Example 1 is expressed as the amount (mg) of sodium methoxide required to neutralize the acid anhydride groups and carboxylic acid contained in 1 g of resin solid. Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 mL of cyclohexanone solvent was added to dissolve. Phenolphthalein test solution was added as an indicator and the mixture was allowed to stand for 30 seconds. The solution was then titrated with 0.1 N sodium methoxide solution until it turned a pale pink color. The acid value was calculated using the following formula (unit: mgCH3ONa / g). Acid value (mgCH3ONa / g)=(5.412×a×F) / S however, S: Amount of sample collected (g) a: Consumption of 0.1N sodium methoxide solution (mL) F: Potency of 0.1N sodium methoxide solution

[0198] The acid anhydride value of Synthesis Example 1 was measured by precisely weighing about 1 g of sample into a stoppered Erlenmeyer flask and dissolving it in 100 mL of 1,4-dioxane solvent. 10 mL of a mixed solution of octylamine, 1,4-dioxane, and water (mixing ratio by mass: 1.49 / 800 / 80) was added, which was greater than the amount of acid anhydride groups in the sample, and the mixture was stirred for 15 minutes to react with the acid anhydride groups. The excess octylamine was then titrated with a mixed solution of 0.02 M perchloric acid and 1,4-dioxane. In addition, a blank was also measured using 10 mL of a mixed solution of octylamine, 1,4-dioxane, and water (mixing ratio by mass: 1.49 / 800 / 80) to which no sample had been added. The acid anhydride value was calculated using the following formula (unit: mgCH3ONa / g). Anhydride value (mgCH3ONa / g) = 0.02 x (BS) x F x 54.12 / W B: Blank titration volume (mL) S: titer of sample (mL) W: sample solid weight (g) F: Potency of 0.02 mol / L perchloric acid

[0199] The ratio of the acid anhydride group and the ring-opened carboxylic acid in Synthesis Example 1 was determined by the following method. Acid anhydride group: Ring-opened carboxylic acid = Acid anhydride value: (Total acid value - Acid anhydride value x 2)

[0200] [Synthesis Example 2] <Synthesis example of polyamide resin (P2)> In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, inlet tube, and thermometer, 324.6 g of Pripol 1009 as a polybasic acid compound with 36 carbon atoms, 25.7 g (0.14 mol) of 5-hydroxyisophthalic acid as a polybasic acid compound with a phenolic hydroxyl group, 138.6 g of Wondamin HA, and 100 g of ion-exchanged water were charged and stirred until the temperature of the heat generation became constant. When the temperature stabilized, the temperature was raised to 110°C, and after confirming the outflow of water, the temperature was raised to 120°C after 30 minutes, and then the dehydration reaction was continued while raising the temperature by 10°C every 30 minutes. When the temperature reached 230°C, the reaction was continued at that temperature for 3 hours, and then the temperature was lowered by holding it under a vacuum of about 2 kPa for 1 hour. Finally, an antioxidant was added to obtain polyamide (A-1) having a weight average molecular weight of 21200, an acid value of 10.6 mgKOH / g, an amine value of 0.3 mgKOH / g, a phenolic hydroxyl value of 16.2 mgKOH / g, and a glass transition temperature of 50° C. Incidentally, the proportion of monomers having C20-60 hydrocarbon groups was 41.4 mol % out of 100 mol % of all monomers subjected to the reaction.

[0201] The phenolic hydroxyl value of Synthesis Example 2 is the amount of phenolic hydroxyl groups contained in 1 g of phenolic hydroxyl group-containing polyamide, expressed as the amount (mg) of potassium hydroxide required to neutralize the acetic acid bonded to the phenolic hydroxyl groups when the phenolic hydroxyl groups are acetylated. The phenolic hydroxyl value was measured in accordance with JIS K0070. In the above, when calculating the phenolic hydroxyl value of the polyamide containing a phenolic hydroxyl group at a terminal carboxylic acid, the calculation is carried out taking into consideration the acid value as shown in the following formula.

[0202] The phenolic hydroxyl value of Synthesis Example 2 was measured as follows. Approximately 1 g of sample is precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 mL of cyclohexanone solvent is added to dissolve it. Then, exactly 5 mL of acetylating agent (a solution of 25 g of acetic anhydride dissolved in pyridine to a volume of 100 mL) is added and stirred for approximately 1 hour. Phenolphthalein test solution is added as an indicator and allowed to stand for 30 seconds. After that, titrate with 0.5 N alcoholic potassium hydroxide solution until the solution turns a pale pink color. The hydroxyl value was calculated by the following formula (unit: mgKOH / g). Hydroxyl value (mgKOH / g) =[{(ba)×F×28.05} / S]+D however, S: Amount of sample collected (g) a: Consumption of 0.5N alcoholic potassium hydroxide solution (mL) b: Amount of 0.5N alcoholic potassium hydroxide solution consumed in the blank experiment (mL) F: Potency of 0.5N alcoholic potassium hydroxide solution D: Acid value (mgKOH / g)

[0203] The acid value of Synthesis Example 2 was determined by the following method. Approximately 1 g of sample was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 mL of cyclohexanone solvent was added to dissolve it. Phenolphthalein test solution was added as an indicator and the solution was held for 30 seconds. Then, the solution was titrated with 0.1N alcoholic potassium hydroxide solution until it turned a pale pink color. The acid value was calculated using the following formula (unit: mgKOH / g). Acid value (mgKOH / g)=(5.611×a×F) / S however, S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic potassium hydroxide solution (mL) F: Potency of 0.1N alcoholic potassium hydroxide solution

[0204] The amine value of Synthesis Example 2 was determined by the following method. Weigh out approximately 1 g of sample precisely into a stoppered Erlenmeyer flask, add 100 mL of cyclohexanone solvent, and dissolve. Dissolve 0.20 g of methyl orange in 50 mL of distilled water separately. The solution was mixed with 0.28g of Xylene Cyanol FF dissolved in 50mL of methanol to prepare an indicator, which was then added in two or three drops and held for 30 seconds. The solution was then titrated with 0.1N alcoholic hydrochloric acid until it turned blue-gray. The amine value was calculated using the following formula (unit: mgKOH / g). Acid value (mgKOH / g)=(5.611×a×F) / S however, S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic hydrochloric acid solution (mL) F: Potency of 0.1N alcoholic hydrochloric acid solution

[0205] The Mw of Synthesis Example 2 was determined by the following method. The Mw was measured using a GPC (gel permeation chromatography) "GPC-101" manufactured by Showa Denko K.K. The GPC is a liquid chromatography that separates and quantifies substances dissolved in a solvent (THF; tetrahydrofuran) based on the difference in their molecular size. The measurement in the present invention was performed using two "KF-805L" (GPC column: 8 mm ID x 300 mm size manufactured by Showa Denko K.K.) columns connected in series under the conditions of a sample concentration of 1 wt%, a flow rate of 1.0 ml / min, a pressure of 3.8 MPa, and a column temperature of 40°C, and the weight average molecular weight (Mw) was determined in polystyrene equivalent. The data was analyzed using the manufacturer's built-in software to calculate the calibration curve, molecular weight, and peak area, and the mass average molecular weight was determined by analyzing the range of retention times from 17.9 to 30.0 minutes.

[0206] The glass transition temperature of polyamide resin (P2) in Synthesis Example 2 was measured as follows: Polyamide resin (P2) from which the solvent had been dried was weighed into an aluminum standard container using a Mettler Toledo "DSC-1" and measured from -80 to 200°C under conditions of a temperature modulation amplitude of ±1°C, a temperature modulation period of 60 seconds, and a temperature rise rate of 2°C / min, and the glass transition temperature was calculated from the differential thermal curve of the reversible component.

[0207] [Synthesis Example 3] <Synthesis example of polyurethane resin (P3)> A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube was charged with 352 parts of a diol having Mn=1002 obtained from adipic acid and 3-methyl-1,5-pentanediol, 32 parts of dimethylolbutanoic acid, 176 parts of isophorone diisocyanate, and 40 parts of toluene, and reacted for 3 hours at 90 ° C. under a nitrogen atmosphere. 300 parts of toluene were added to this to obtain a solution of a urethane prepolymer having an isocyanate group at the end. Next, 810 parts of the obtained urethane prepolymer solution were added to a mixture of 32 parts of isophorone diamine, 4 parts of di-n-butylamine, 342 parts of 2-propanol, and 576 parts of toluene, and reacted at 70 ° C. for 3 hours to obtain a solution of a polyurethane polyurea resin having Mw=35,000 and an acid value of 21 mgKOH / g. To this were added 144 parts of toluene and 72 parts of 2-propanol to obtain a polyurethane polyurea resin solution with a solid content of 50%.

[0208] The Tg of Synthesis Example 3 was measured by differential scanning calorimetry (Mettler Toledo's "DSC-1"). The Mw of Synthesis Example 3 was measured by the same method as Synthesis Example 1. The acid value was measured by dissolving 1 g of thermosetting resin in 40 mL of methyl ethyl ketone and using an automatic titration device "AT-510" manufactured by Kyoto Electronics Manufacturing Co., Ltd., connected to the same company's "APB-510-20B" as a burette. Potentiometric titration was performed using a 0.1 mol / L ethanolic KOH solution as the titration reagent, and the number of mg of KOH per 1 g of resin was calculated.

[0209] [Synthesis Example 4] <Synthesis of polyimide resin (P4)> In a four-neck flask equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, an inlet tube, and a thermometer, 378.7 g of a dimer diamine (Priamine 1075) having 36 carbon atoms as a polyamine compound, 380.0 g of bisphenol A type dianhydride (4,4'-[propane-2,2-diylbis(1,4-phenyleneoxy)]diphthalic dianhydride) (BISDA-1000) as a tetracarboxylic acid anhydride, and 1100 g of cyclohexanone as a solvent were charged and stirred until uniform. After becoming uniform, the temperature was raised to 110 ° C., and after 30 minutes, the temperature was raised to 140 ° C., and when the temperature reached 140 ° C., the reaction was continued at that temperature for 10 hours to continue the dehydration reaction. Next, an antioxidant was added to obtain a polyimide resin having a weight average molecular weight of 54,000, an acid value of 6.4 mg KOH / g, and an amine value of 0.3 mg KOH / g. The acid value, amine value, and weight average molecular weight of Synthesis Example 4 and Synthesis Examples 5 and 6 described below were determined in the same manner as in Synthesis Example 2.

[0210] [Synthesis Example 5] <Synthesis of polyimide resin (P4)> In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, inlet tube, and thermometer, 358.0 g of Priamine 1075 as a polyamine compound, 214.8 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) as a tetracarboxylic anhydride, and 823 g of xylene as a solvent were charged and stirred until homogeneous. When homogeneous, the temperature was raised to 110°C, and after 30 minutes, the temperature was raised to 140°C. When the temperature reached 140°C, the reaction was continued at that temperature for 10 hours to continue the dehydration reaction. Next, an antioxidant was added to obtain a polyimide resin with a weight average molecular weight of 16,000, an acid value of 4.3 mgKOH / g, and an amine value of 0.2 mgKOH / g.

[0211] [Synthesis Example 6] <Synthesis of polyimide resin (P4)> In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, inlet tube, and thermometer, 371.6 g of Priamine 1075 as a polyamine compound, 226.5 g of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (OPDA) as a tetracarboxylic anhydride, and 860 g of xylene as a solvent were charged and stirred until homogeneous. When homogeneous, the temperature was raised to 110°C, and after 30 minutes, the temperature was raised to 140°C. When the temperature reached 140°C, the reaction was continued at that temperature for 10 hours to continue the dehydration reaction. Next, an antioxidant was added to obtain a polyimide with a weight average molecular weight of 30,000, an acid value of 8.1 mgKOH / g, and an amine value of 0.4 mgKOH / g.

[0212] [Preparation of sheet-shaped thermosetting resin composition] (Examples 1 to 17) Resin, curing agent and solvent (methyl ethyl ketone) were mixed in the blending ratio (solid mass parts) shown in Table 1, and then a thermally conductive filler was added and stirred with a disperser to obtain a thermosetting resin composition with a solid content of 60 mass%. Next, each of the thermosetting resin compositions of Examples 1 to 17 was applied onto a release sheet and dried to obtain a sheet 1 in which one side of the resin layer was covered with a release sheet. Thereafter, another set of sheets 1 was obtained in the same manner, and the resin layer sides were overlapped to form a release sheet on both sides of the resin layer, that is, a sheet-like thermosetting resin composition with a double-sided release sheet in which the overlapped resin layers were sandwiched between the release sheets (hereinafter also referred to as sheet 2) was formed.

[0213] [Dielectric constant] A test piece for evaluation was prepared by removing the release sheet on one side of the above-mentioned sheet 2 of each example, heat curing for 1 hour at 180° C., and then removing the release sheet on the other side. The relative dielectric constant and dielectric loss tangent of this test piece were determined by a cavity resonator method using a dielectric constant measuring device manufactured by AET Corporation at a measurement temperature of 23° C. and a measurement frequency of 5 GHz. A: The dielectric constant is 3.2 or less. B: The dielectric constant is greater than 3.2 and less than or equal to 3.5. C: The dielectric constant is greater than 3.5 and less than or equal to 4.0. D: Dielectric constant is greater than 4.0.

[0214] [Dissipation factor] A: The dielectric tangent is 0.003 or less. B: The dielectric tangent is greater than 0.003 and less than or equal to 0.005. C: The dielectric tangent is greater than 0.005 and less than or equal to 0.010. D: The dielectric tangent is greater than 0.010.

[0215] [Thermal Conductivity] <Thermal conductivity> The surface of the sheet 1 of each example that was not covered with the release sheet was covered with the same release sheet as above, and heat pressed at 180°C for 1 hour at a pressure of 1 MPa. The release sheets on both sides were then peeled off to obtain a single-layer thermally conductive sheet (hereinafter referred to as a measurement sample). The obtained measurement sample was cut into 15 mm squares, and the surface of the measurement sample was gold-deposited and carbon-coated with carbon spray. Next, the thermal diffusivity in a sample environment of 25°C was measured using a xenon flash analyzer LFA447Nano Flash (manufactured by NETZSCH). The specific heat capacity was also measured using a high-sensitivity differential scanning calorimeter DSC220C manufactured by SII Nano Technology Co., Ltd. Furthermore, the density was calculated using the underwater displacement method. The thermal conductivity was calculated based on the following formula, and the results were judged according to the following criteria. Conductivity (W / m K) = Density (g / cm 3 ) × specific heat (J / kg K) × thermal diffusivity (mm 2 / s). A Thermal conductivity is 5 W / m K or more. B Thermal conductivity is 2 W / m K or more and less than 5 W / m K. C Thermal conductivity is 0.5 W / m K or more and less than 2 W / m K. D Thermal conductivity is less than 0.5 W / m / K.

[0216] <Adhesiveness> The above-mentioned sheet 2 of each example was cut to a size of 65 mm x 65 mm, the release sheet on one side was removed, and the sheet was attached to a polyimide film ["Kapton 300H" manufactured by Toray DuPont Co., Ltd.] having a thickness of 75 μm, and then the release sheet on the other side was removed, and the sheet was attached to a copper-clad laminate having a thickness of 45 μm, and laminated at 80°C, and then pressure-bonded for 5 minutes under the conditions of 160°C and 1.0 MPa. Furthermore, the test piece was thermally cured at 160°C for 1 hour to prepare a test piece for evaluation. The test piece was cut to a width of 10 mm and a length of 65 mm, and a T-peel peel test was performed at a pulling speed of 300 mm / min under an atmosphere of 23°C and 50% relative humidity to measure the adhesive strength (N / cm). This test was performed to evaluate the adhesive strength of the cured product of the thermosetting resin composition for thermal conductive material when used at room temperature, and the results were judged according to the following criteria. A: The adhesive strength is 15 (N / cm) or more. B: The adhesive strength is 10 (N / cm) or more and less than 15 (N / cm) C: The adhesive strength is 5 (N / cm) or more and less than 10 (N / cm). D...The adhesive strength is less than 5 (N / cm).

[0217] The curing agents used in this example are as follows: (hardening agent) Curing agent 1: TETRAD-X, manufactured by Mitsubishi Gas Chemical Company, a tetrafunctional polyfunctional glycidylamine compound Hardener 2: 24A-100: Biuret form of hexamethylene diisocyanate (hereinafter abbreviated as HDI), manufactured by Asahi Kasei Chemical Corporation Hardener 3: ZC700, Matsumoto Fine Chemical Co., Ltd., 4-functional Zr chelate compound Hardener 4: Epoxy resin, Mitsubishi Chemical Corporation, JER1031S (Thermal conductive filler) Boron nitride: PTX60: Granulated boron nitride filler (PTX-60 manufactured by Momentive) with an average compressive force of 3.6 mN required for a compressive deformation rate of 10% and an average particle size of 55 to 65 μm. Alumina: ao509: spherical alumina with an average circularity of 0.99 and an average particle size of 10 μm (Admafine AO-509 manufactured by Admatechs Co., Ltd.); (Other fillers) PTFE: PTFE "CERAFLOUR981 (average particle size D50: 3 μm)" manufactured by BYK (Flame retardant) Flame retardant 1: Aluminum phosphinate

[0218] [Table 1]

[0219] [Note] This specification also discloses the invention of the following technical concept that can be understood from the above-mentioned embodiment. (Appendix 1) An anisotropic conductive adhesive comprising a thermosetting resin composition for a thermal conductive material, the thermosetting resin composition containing a binder component including a thermosetting resin and a curing agent, and a thermally conductive filler, and a conductive filler added thereto, The binder component is a binder component (I) containing a styrene-based elastomer (P1) having a carboxylic acid anhydride group and a polyisocyanate component (C1) that reacts with the anhydride group; A binder component (II) containing a polyamide resin (P2) having a phenolic hydroxyl group in a side group and a tri- or higher functional compound (C2) capable of reacting with the phenolic hydroxyl group, or a binder component (III) containing a polyurethane resin (P3) having a carboxyl group and an epoxy compound (C3) capable of reacting with the carboxyl group, The cured product obtained by curing the thermosetting resin composition for a thermal conductive material is The dielectric constant is 4.0 or less at a frequency of 5 GHz and 23°C. The dielectric tangent is 0.010 or less at a frequency of 5 GHz and 23°C. Anisotropic conductive adhesive.

Claims

1. A thermosetting resin composition for a thermal conductive material, comprising a binder component including a thermosetting resin and a curing agent, and a thermally conductive filler, The binder component is A binder component (I) containing a styrene-based elastomer (P1) having a carboxylic acid anhydride group and a polyisocyanate component (C1) that reacts with the anhydride group; A binder component (III) containing a polyurethane resin (P3) having a carboxyl group and a tri- or higher functional epoxy compound (C3) which is a glycidyl ether type epoxy resin capable of reacting with the carboxyl group, or a binder component (IV) containing a polyimide resin (P4) having a reactive functional group and including a hydrocarbon group having 20 to 60 carbon atoms, and a bifunctional or higher functional compound (C4) that reacts with the reactive functional group, The cured product obtained by curing the thermosetting resin composition for a thermal conductive material is The dielectric constant is 4.0 or less at a frequency of 5 GHz and 23° C., The dielectric tangent is 0.010 or less at a frequency of 5 GHz and 23° C., The styrene-based elastomer (P1) is a block copolymer having at least one of a structural unit derived from an olefin and a structural unit derived from a conjugated diene, and a structural unit derived from styrene; and the polyisocyanate component (C1) is an isocyanate group-containing compound having two or more isocyanates; The polyurethane resin (P3) is a polyurethane polyurea resin, the polyimide resin (P4) contains structural units derived from an aromatic carboxylic acid polyanhydride and structural units derived from a polyamine compound having a hydrocarbon group having 20 to 60 carbon atoms, and 70 mass % or more of the hydrocarbon group having 20 to 60 carbon atoms is a group derived from a dimer skeleton; the reactive functional groups are amine and / or anhydride groups, The thermosetting resin composition for a thermal conductive material, wherein the di- or higher functional compound (C4) is an epoxy compound.

2. 2. The thermosetting resin composition for a thermal conductive material according to claim 1, wherein the thermally conductive filler is at least one selected from the group consisting of alumina, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, calcium oxide, magnesium oxide, zinc oxide, beryllia, aluminum nitride, boron nitride, fused silica, crystalline silica, non-crystalline silica, silicon carbide, silicon nitride, titanium carbide, and diamond.

3. 3. The thermosetting resin composition for a thermal conductive material according to claim 1, which is in any one of a powder form, a film form, a sheet form, a plate form, a pellet form, a paste form, and a liquid form.

4. A cured product of the thermosetting resin composition for thermal conductive materials, obtained by curing the thermosetting resin composition for thermal conductive materials according to any one of claims 1 to 3 by heating.

5. An electronic part comprising a cured product of the thermosetting resin composition for thermal conductive materials according to claim 4.

6. The electronic component according to claim 5 , wherein the cured product is a circuit board or an insulating layer formed on a circuit board.

7. The electronic component according to claim 5 , wherein the cured product is used as an adhesive or a sealant.

8. An electronic device having the electronic component according to any one of claims 5 to 7 mounted thereon.

Citation Information

Patent Citations

  • Heat-resistant elastic material

    JP2005209955A

  • Boron nitride powder and use thereof

    JP2014040341A

  • Electromagnetic wave shield sheet, electromagnetic wave shield wiring circuit board and electronic apparatus

    JP2017147276A

  • Laminate, method for manufacturing the same, and resin film with adhesive layer

    JP2017163131A

  • Thermally-conductive insulating sheet and composite member

    JP2019029269A